Synthetic hydrogel composites
By infiltrating and annealing hydrogels into a nanofiber network, a highly crystalline cellulose-reinforced hydrogel is formed, solving the problems of joint wear and stress distribution in traditional materials. This provides a cartilage repair material with similar mechanical properties to cartilage and low wear, suitable for knee resurfacing.
Patent Information
- Application Number
- CN202380047565.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-21
- Filing Date
- 2023-05-04
- Publication Date
- 2025-01-14
AI Technical Summary
In the treatment of osteoarthritis and articular cartilage damage, existing technologies rely on traditional orthopedic materials such as cobalt-chromium alloys or ultra-high molecular weight polyethylene, which have high coefficients of friction and high hardness, leading to joint wear and abnormal stress distribution. There is a lack of cartilage repair materials with low failure rates, low invasiveness, and wide availability.
A cellulose-reinforced hydrogel material is used. By infiltrating the hydrogel into a nanofiber network and then drying, annealing, and rehydrating it, a hydrogel with high crystallinity and low water content is formed. This mimics the mechanical and tribological properties of cartilage, enhancing its strength and wear resistance, and fixing it to the implant surface.
It achieves similar modulus, coefficient of friction and wear resistance to cartilage, can withstand high compressive and shear stresses during joint movement, provides a cartilage repair material with low failure rate and low invasiveness, and reduces wear on the relative cartilage surface.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Priority claim
[0001] This patent application claims priority to U.S. Patent Application No. 17 / 845,881, filed on June 21, 2022, entitled “SYNTHETIC HYDROGEL COMPOSITE,” and U.S. Provisional Patent Application No. 63 / 338,439, filed on May 4, 2022, entitled “SYNTHETIC HYDROGEL COMPOSITE,” each of which is incorporated herein by reference in its entirety. Incorporated by Reference
[0002] All publications and patent applications mentioned in this specification are herein incorporated by reference in their entirety to the same extent as if each individual publication or patent application was specifically and individually indicated to be incorporated by reference. background
[0003] In the U.S., about 900,000 people suffer from articular cartilage damage at the end of bones every year. Osteoarthritis (OA) is an example of degenerative joint disease, which is a common cause of disability. Articular cartilage damage (articular cartilage lesion) most often occurs in the knee, and can cause severe pain (debilitating pain). Cartilage lacks blood vessels and has very limited healing ability. A method for treating cartilage damage is to try to make cartilage grow again with the technology such as microfracture (microfracture) or autologous chondrocyte implantation (autologous chondrocyte implantation). Unfortunately, these methods have high failure rate (failure rate), prolonged convalescence time, and show reduced efficacy in elderly patients. Implanting fresh allogeneic osteochondral allografts (osteochondralallograft) can accelerate recovery because they eliminate the need to regenerate cartilage. Unfortunately, the small supply of fresh allogeneic transplants limits the number of these programs. The failure of these treatment strategies usually leads to more invasive total knee replacement. While total knee replacement may be successful in older patients, it may not be suitable for younger patients, for whom the implant may fail during their lifetime, thus requiring a second invasive procedure. Therefore, there is a clear need for a minimally invasive treatment option that treats cartilage damage with a low failure rate, allows for rapid recovery, and is widely available.
[0004] In view of the need for less invasive alternatives to total knee replacement to treat OA, efforts are currently underway to replace damaged cartilage with devices made of traditional orthopedic materials such as cobalt-chromium alloys or ultra-high molecular weight polyethylene. However, these materials have a much higher coefficient of friction (COF) than cartilage and may cause unacceptable levels of wear on the opposing cartilage surfaces. In addition, these materials are much harder than cartilage and may therefore cause abnormal stress distribution in the joint, which potentially promotes damage to the surrounding cartilage.
[0005] Hydrogels, polymer networks swollen with water, are promising synthetic materials for replacing cartilage because they can be made to have mechanical and tribological properties similar to natural cartilage. However, there is a need to improve the physical properties of hydrogels to withstand the wear and tear that implants may encounter. For example, there is a need for hydrogels that are at the high end of the reported cartilage strength range while having a modulus, coefficient of friction, and wear resistance similar to that of cartilage. Methods, hydrogel compositions, and devices (e.g., implants) that can address these needs are described herein. Overview of public content
[0006] The present disclosure generally relates to artificial cartilage materials including hydrogel composites in implants suitable for cartilage repair, and methods for attaching the hydrogel composites to implant surfaces.
[0007] The hydrogel material used as the artificial cartilage in the implant is described herein.Hydrogel can be injected into nanofiber material (for example, nanofiber network) and be attached to the surface of implant, such as porous base.Composite hydrogel has the physical properties of the physical properties of the healthy cartilage close to or exceeding that combined with bone, such as strength, modulus, wear resistance and friction coefficient (COF).The method can be related to strengthening process, to increase the crystallinity of hydrogel and reduce the water content of hydrogel, so as to improve the mechanical properties of hydrogel for realizing cartilage replacement.As described herein, the strengthening of hydrogel can include one or more steps in drying, annealing and rehydration, to affect the crystalline structure of hydrogel.The method can also be related to the surface of nanofiber material being fixed to implant, hydrogel being infiltrated into nanofiber network, and hydrogel being annealed.
[0008] Methods for producing synthetic cartilage by infiltrating a hydrogel into a nanofiber network to mimic cartilage are described in International Patent Application No. PCT / US2021 / 040031, which is incorporated herein by reference in its entirety. The methods described herein can be used to form hydrogels that match or exceed the high end of the cartilage strength range while having moduli, coefficients of friction, and wear resistance similar to those of cartilage.
[0009] Hydrogels and methods for preparing and using the hydrogels to simulate or replace cartilage are described herein, and the hydrogels can be interlaced with nanofiber networks such as cellulose nanofiber networks. The hydrogel incorporated can have a crystalline structure that gives the hydrogel high tensile strength and / or compressive strength. In some embodiments, the enhanced hydrogel used in the implant described herein can include a cross-linked cellulose nanofiber network; and a hydrogel injected into the gap region of the cross-linked cellulose nanofiber network, wherein the hydrogel has a crystallinity of 20% or more. In some embodiments, the hydrogel includes polyvinyl alcohol (PVA). In any of these embodiments, the hydrogel can exclude (or substantially exclude) PAMPS. The hydrogel can be> 90% (e.g.,> 92%,> 93%,> 94%,> 95%,> 96%,> 97%,> 98%,> 99%, etc.) of PVA that has been annealed as described herein.
[0010] As demonstrated herein, the crystallites formed during annealing strengthen otherwise amorphous polymer hydrogels by acting as crosslinks that redistribute applied stresses and hinder crack propagation. The crystallites also increase the solid content and strength of the hydrogel by reducing the amount of water absorbed by the PVA after annealing.
[0011] Implants are described herein, and the implants include: an implant body and a cellulose-enhanced hydrogel material, the cellulose-enhanced hydrogel material comprising: a cross-linked cellulose nanofiber network that is bonded to the porous surface of the implant body by a cement; and a hydrogel impregnated in the cross-linked cellulose nanofiber network, wherein the hydrogel has a crystallinity of 20% or greater. The implant body can include a porous surface. For example, the implant body can be a titanium body with a porous surface facing the bone and a non-porous surface facing the hydrogel.
[0012] The hydrogels described herein can have a water content that contributes to imparting high tensile and / or compressive strength to the hydrogel. In some embodiments, the hydrogel can have at least 20% (wt.%) water by weight and have a tensile strength that exceeds the tensile strength of cartilage, e.g., greater than 40 megapascals (MPa).
[0013] The composition of the interstitial hydrogel can be selected to maximize crystallinity. For example, some hydrogel polymers and / or polymer blends have been found to hinder crystal formation, thereby reducing the tensile and compressive strength of the composite hydrogel.
[0014] Typically, the hydrogel may include one or more polymers that contribute to the formation of a crystalline structure. In some embodiments, the hydrogel may include polyvinyl alcohol (PVA). In some cases, the hydrogel may include only one type of polymer. In some variations, the hydrogel includes one or more of the following items: polyvinyl alcohol (PVA), poly (2-acrylamide-2-methyl-1-propanesulfonic acid sodium salt) (PAMPS), poly (N, N'-dimethylacrylamide) (PDMAAm), copolymers of 1-vinylimidazole and methacrylic acid, amphiphilic triblock copolymers, polyampholyte hydrogels (polyampholytehydrogel), PVA-tannic acid hydrogels, poly (N-acryloyl) glycinamide hydrogels, polyacrylic acid-acrylamide-C18 hydrogels, guanine-boric acid enhanced PDMAAm, polyelectrolyte hydrogels, poly (acrylonitrile-to-l-vinylimidazole) hydrogels (e.g., mineralized poly (acrylonitrile-to-l-vinylimidazole) hydrogels), polyacrylic acid-Fe 3+ - chitosan hydrogel, poly(methacrylic acid) gel, graphene oxide / xonotlite reinforced polyacrylamide (PAAm) gel, poly(stearyl methacrylate)-polyacrylic acid gel, annealed PVA-polyacrylic acid hydrogel, supramolecular hydrogel from multiurea linkage segmented copolymer, polyacrylonitrile-PAAm hydrogel, microsilica reinforced DMA gel, agar-polyhydroxyethyl methacrylate gel, polyacryloylethyltrimethylammonium chloride hydrogel, poly(3-methacrylamido)propyl-trimethylammonium chloride hydrogel, poly(sodium p-styrene sulfonate) hydrogel, polyethylene glycol diacrylate hydrogel, and polyethylene glycol hydrogel. In some cases, excluding PAMPS (e.g., having no PAMPS, having less than 0.1%, less than 0.5%, less than 1% PAMPS, etc.) may be beneficial.
[0015] The nanofiber network may include a cellulose nanofiber network. The nanofiber network may include a cross-linked cellulose nanofiber network. In certain embodiments, the nanofiber network includes bacterial cellulose (BC). Additionally or alternatively, the nanofiber network may include at least one of electrospun polymer nanofibers, poly(vinyl alcohol) (PVA) nanofibers, aramid nanofibers, aramid-PVA nanofibers, wet-spun silk protein nanofibers, chemically cross-linked cellulose nanofibers, and polycaprolactone (PCL) fibers.
[0016] The cellulose-enhanced hydrogel may include: a cellulose nanofiber network; and a hydrogel impregnated in the cellulose nanofiber network, wherein the hydrogel has a crystallinity of 20% or greater. The cellulose-enhanced hydrogel material may have a tensile strength of 40 MPa or greater. The cellulose-enhanced hydrogel material may have a compressive strength of 59 MPa or greater.
[0017] Described herein are cellulose-reinforced hydrogels comprising a water content of at least 20 wt.% and a compressive strength exceeding 59 MPa. The cellulose-reinforced hydrogel may comprise bacterial cellulose and / or a hydrogel comprising polyvinyl alcohol (PVA).
[0018] A method for forming a cellulose-enhanced hydrogel is described herein, the method comprising: infiltrating a hydrogel in a cellulose nanofiber network to form a cellulose-enhanced hydrogel; and annealing the hydrogel to increase the crystalline content of the hydrogel. Annealing the hydrogel may include heating the cellulose-enhanced hydrogel. Annealing the hydrogel may include heating the cellulose-enhanced hydrogel to reduce the water content of the hydrogel. In some embodiments, the cellulose-enhanced hydrogel may be heated to a temperature ranging from 90°C-140°C. Annealing the hydrogel may include rehydrating the hydrogel. Rehydrating the hydrogel may include increasing the water content of the hydrogel to at least 20 wt.%. The method may also include removing excess hydrogel from the surface of the cellulose nanofiber network. Removing excess hydrogel may include removing excess hydrogel by hand or by molding the cellulose-enhanced hydrogel.
[0019] The present invention describes an implant for knee resurfacing, which includes: a top bearing surface, the top bearing surface includes a cellulose-reinforced hydrogel, the cellulose-reinforced hydrogel includes: a cellulose nanofiber network; and a hydrogel impregnated in the cellulose nanofiber network, wherein the hydrogel has a crystallinity of 20% or greater.
[0020] Hydrogels (eg, cellulose reinforced hydrogels) can be attached to metal substrates with shear strengths exceeding 0.2 MPa.
[0021] When used for partial knee resurfacing, the implant can be configured to wear the opposing cartilage surface to a degree not significantly greater than the degree to which cartilage wears cartilage. The top bearing surface of the implant can have a coefficient of friction (COF) that is not statistically different from that of cartilage.
[0022] The implants described herein can be configured as medical implants and can include a tissue engaging portion (e.g., a bone engaging portion, such as a rod, a sieve, a nail, etc.). The first surface of the implant to which the nanofiber network can be fixed can be porous. For example, the first surface can be greater than 40% porous with a depth of 1 mm or greater.
[0023] The nanofiber network can be fixed to the implant (e.g., fixed to the porous surface of the implant) by any suitable method. For example, the nanofiber network can be fixed to the implant by a cement such as α-TCP cement. In some embodiments, the cement comprises one or more of the following items: zinc oxide eugenol, glass ionomer, calcium silicate, polycarboxylate cement, zinc phosphate, resin-based (dental) cement such as acrylate or methacrylate resin cement (which can be included in a silicate or other type of filler in an organic resin matrix (e.g., methacrylate cement, such as "RelyX™ Unicem 2 self-adhesive resin cement" or "RelyX™ Ultimate adhesive resin cement")), and resin-modified glass ionomer cement. The cement can include an adhesive such as, but not limited to, phosphoserine (PPS). In some variations, the cement can include particles for reinforcement, such as stainless steel particles (e.g., stainless steel powder, SSP).
[0024] The cement may extend from the first surface into the nanofiber network by at least 5 microns (e.g., 6 microns or greater, 7 microns or greater, 8 microns or greater, 10 microns or greater, 15 microns or greater, 20 microns or greater, etc.). The cement may not be bonded to the hydrogel. In some embodiments, cementation may be accomplished (and the cement solidified or dried) prior to impregnation with the hydrogel.
[0025] The cement may be bonded to the nanofiber network but not directly bonded to the hydrogel. This may be a result of a method of forming a network-enhanced hydrogel in which a nanofiber network (e.g., a cellulose nanofiber network) is first fixed (e.g., cemented) to the implant body before impregnating the hydrogel. The cement may be cured to the nanofiber network so that it is not directly bonded to the hydrogel.
[0026] Other adhesives may include surgical adhesives such as cyanoacrylates, gelatin / resorcinol / formaldehyde (GRF), and / or fibrin.
[0027] The implant can be formed of any suitable biocompatible material. For example, the surface of the implant body can be titanium. The surface of the implant body can be one or more of the following: stainless steel alloy, titanium alloy, Co-Cr alloy, tantalum, gold, niobium, bone, Al oxide, Zr oxide, hydroxyapatite, tricalcium phosphate, sodium calcium phosphosilicate, poly (methyl methacrylate), polyetheretherketone, polyethylene, polyamide, polyurethane or polytetrafluoroethylene.
[0028] As mentioned, the attachment surface of wherein fixing nanofiber network can be porous.Selectively, the attachment surface can be non-porous.For example, the attachment surface can be 20% or more (30% or more, 40% or more, 50% or more, 60% or more, 70% or more, etc.) porous, with a depth of 0.5 mm or more (for example, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm or more, etc.).As used herein, the surface is a porous percentage (for example, the percentage porosity on the surface) that can refer to the surface percentage of the missing of the inner surface at a certain depth, forming open space in the surface.These open spaces can refer to holes, and some of these holes can be connected to each other (for example, fluid connection).The attachment surface can be generally referred to as the top bearing surface in this article, because it can be configured to contact other surfaces (for example, bone surface, etc.), and can be added to the load-bearing surface.
[0029] In any of these devices (e.g., apparatus, systems, including implants), at least a portion of the nanofiber network can be mineralized. For example, at least a portion, such as a region near an interface with a surface, can be mineralized with hydroxyapatite. The mineralization can extend from the surface into the nanofiber network to at least 5 microns (e.g., at least 7 microns, at least 8 microns, at least 9 microns, at least 10 microns, at least 15 microns, at least 20 microns, etc.).
[0030] Typically, the nanofiber network can be coupled to the top support surface of the implant. The cross-linked cellulose nanofiber network can be attached to the top load surface by clamping and / or by an adhesive. For example, the nanofiber network can be bonded to the top load surface by an adhesive; in some embodiments, the adhesive is not bonded to the hydrogel; the adhesive is only bonded to the nanofiber network. Alternatively, in some embodiments, the nanofiber network can be coupled to the implant so that the nanofiber network is fixed to the top support surface without using a chemical adhesive such as an epoxy resin. Alternatively, the nanofiber network can be fixed to the top support surface by a clamp. For example, the clamp can fix the nanofiber network (e.g., one or more BC sheets) on the top support surface around the periphery of the top support surface. Therefore, typically, the use of an adhesive (such as an epoxy resin) is optional.
[0031] Any suitable implant can be used.The surface of the implant (e.g., top bearing surface, which can be equivalently referred to as bearing surface) can be titanium, stainless steel, etc., at least in the region where the nanofiber network is attached thereto. The bearing surface (e.g., top bearing surface) can be convex, flat, concave or some mixture of these. For example, the surface of the implant body can include one or more of the following: stainless steel alloy, titanium alloy, Co-Cr alloy, tantalum, gold, niobium, bone, Al oxide, Zr oxide, hydroxyapatite, tricalcium phosphate, sodium calcium phosphosilicate, poly (methyl methacrylate), polyetheretherketone, polyethylene, polyamide, polyurethane or polytetrafluoroethylene.
[0032] Also described herein are methods of making and / or using these implants. For example, methods of attaching a hydrogel to a surface are described herein so that the hydrogel is fixed to the surface with a shear strength greater than 1 MPa. Any of these methods may include: infiltrating the hydrogel in a cellulose nanofiber network to form a cellulose-enhanced hydrogel; and annealing the hydrogel to increase the crystalline content of the hydrogel. For example, annealing the hydrogel may include heating the cellulose-enhanced hydrogel. In some embodiments, annealing the hydrogel may include heating the cellulose-enhanced hydrogel to reduce the water content of the hydrogel. For example, the cellulose-enhanced hydrogel may be heated to a temperature ranging from 90°C-140°C. In some cases, annealing the hydrogel may include rehydrating the hydrogel. Rehydrating the hydrogel may include increasing the water content of the hydrogel to at least 20 wt.%. The method may also include removing excess hydrogel from the surface of the cellulose nanofiber network. Removing excess hydrogel may include removing excess hydrogel by hand or by molding the cellulose-enhanced hydrogel.
[0033] In some embodiments, the outer surface of the hydrogel can be formed to be smooth (e.g., to have a roughness less than 30 microns). For example, the methods described herein can include mechanically polishing the outer surface of the hydrogel to a roughness less than 30 microns. In some cases, the outer surface can be formed to be smooth by molding, including using a smooth mold to mold a heated polymer. For example, infiltrating the nanofiber network with a hydrogel can include molding the hydrogel so that the outer surface of the hydrogel has a roughness less than 30 microns. Molding the outer surface can also allow the manufacturer to form the outer surface into any desired shape. For example, the shape can be concave, convex, saddle-shaped, etc. Any desired shape (and smoothness) can be formed, for example, by molding and / or polishing.
[0034] In any of these methods, fixing (e.g., drying) the nanofiber network may include fixing (such as clamping and / or bonding) a freeze-dried nanofiber network. As mentioned above, any of these devices and methods may use a dry nanofiber network comprising a cellulose nanofiber network. The dry nanofiber network may include at least one of the following items: electrospun polymer nanofibers, poly(vinyl alcohol) (PVA) nanofibers, aramid nanofibers, aramid-PVA nanofibers, wet-spun protein nanofibers, chemically cross-linked cellulose nanofibers or polycaprolactone (PCL) fibers.
[0035] Any of the methods described herein may include rehydrating the nanofiber network, including rehydrating the nanofiber network after the nanofiber network is secured to a surface of an implant.
[0036] Any of these methods may include mineralizing at least a portion of the nanofiber network adjacent to the surface.
[0037] Implants for knee resurfacing or partial knee resurfacing are described herein. For example, a top bearing surface of the implant can include a hydrogel having a water content of at least 20 wt.%, wherein the hydrogel is attached to a metal base with a shear strength exceeding 0.2 MPa.
[0038] Any of the methods described herein may include mechanically polishing the outer surface of the hydrogel (e.g., cellulose-reinforced hydrogel) to a roughness of less than 50 microns (e.g., less than 50 microns, less than 40 microns, less than 30 microns, less than 25 microns, less than 20 microns, less than 15 microns, less than 10 microns, etc.). Mechanical polishing may include grinding the hydrogel attached to the surface as described herein with fine grits and paper or equivalent.
[0039] Any of these methods may include rehydrating the nanofiber network. The nanofiber network may be rehydrated prior to impregnation with the hydrogel, or the impregnation may rehydrate the nanofiber network.
[0040] For example, implants are described herein, comprising: an implant body having a top support surface; an anchoring base (which may extend from the back of the top support surface); and a cellulose-enhanced hydrogel comprising: a cross-linked cellulose nanofiber network fixed on the top support surface of the implant body; and a gap hydrogel portion within the gap region of the cross-linked cellulose nanofiber network, wherein the gap hydrogel portion has a crystallinity of 20% or greater. The gap hydrogel portion may be polyvinyl alcohol (PVA). The cellulose-enhanced hydrogel may include at least 20% water by weight. The cellulose-enhanced hydrogel may have a tensile strength of more than 40 MPa. The cross-linked cellulose nanofiber network may be chemically cross-linked. The cross-linked cellulose nanofiber network may include bacterial cellulose (BC). The cellulose-enhanced hydrogel may have a compressive strength of more than 59 MPa. The cross-linked cellulose nanofiber network may be fixed on the top support surface by a fixture. In some embodiments, the cross-linked cellulose nanofiber network includes one or more bacterial cellulose (BC) sheets, which are held on the top support surface by a fixture fixed to the lip or rim of the top support surface. The fixture can be used to fix the cross-linked cellulose nanofiber network without epoxy resin. Alternatively, any of these implants can include an adhesive.
[0041] Also described herein is a method for forming an implant with a cellulose-enhanced hydrogel, the method comprising: attaching a cross-linked cellulose nanofiber network to the top support surface of the implant; infiltrating a hydrogel component in the interstitial region of the cross-linked cellulose nanofiber network to form the cellulose-enhanced hydrogel; and annealing the cellulose-enhanced hydrogel so that the crystal content of the hydrogel component has a crystallinity of 20% or greater. The hydrogel component may include polyvinyl alcohol (PVA). Annealing the cellulose-enhanced hydrogel may include heating the cellulose-enhanced hydrogel. For example, annealing the cellulose-enhanced hydrogel may include heating the cellulose-enhanced hydrogel to reduce the water content of the cellulose-enhanced hydrogel. In some embodiments, the cellulose-enhanced hydrogel is heated to a temperature ranging from 90°C-140°C. Annealing the cellulose-enhanced hydrogel may include rehydrating the cellulose-enhanced hydrogel. Rehydrating the cellulose-enhanced hydrogel may include increasing the water content of the cellulose-enhanced hydrogel to at least 20 wt.%. Any of these methods may include removing excess hydrogel components from the surface of the cross-linked cellulose nanofiber network. For example, excess hydrogel components may be removed by hand or by molding the cellulose-enhanced hydrogel. In any of these embodiments, the cross-linked cellulose nanofiber network may comprise bacterial cellulose (BC).In some embodiments, attaching the cross-linked cellulose nanofiber network to the top support surface comprises clamping the cross-linked cellulose nanofibers around a perimeter of the top support surface.
[0042] Also described herein is an implant for knee resurfacing, the implant comprising: a top bearing surface comprising a cellulose-enhanced hydrogel comprising: a cellulose nanofiber network; and a hydrogel component impregnated in the cellulose nanofiber network, wherein the hydrogel component has a crystallinity of 20% or greater. The hydrogel component may comprise polyvinyl alcohol (PVA). The cellulose-enhanced hydrogel may comprise at least 20% water by weight. The cellulose-enhanced hydrogel may have a tensile strength of more than 40 MPa. The cellulose-enhanced hydrogel may be attached to a metal base of the top bearing surface with a shear strength of more than 0.2 MPa. The top bearing surface may have a coefficient of friction that is statistically no greater than the coefficient of friction (COF) of cartilage.
[0043] Generally, the methods and apparatus described herein can be used with any methods, apparatus, and compositions described in International Patent Application No. PCT / US2021 / 040031, filed on July 1, 2021, entitled “NANOFIBERREINFORCEMENT OF ATTACHED HYDROGELS,” which is incorporated herein by reference in its entirety.
[0044] All methods and apparatus described herein, in any combination, are contemplated herein and can be used to achieve the benefits as described herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] A better understanding of the features and advantages of the methods and apparatus described herein will be obtained by referring to the following detailed description and the accompanying drawings, which set forth illustrative embodiments.
[0046] Figure 1A is a diagram of an exemplary process for attaching a hydrogel to a porous substrate by a nanofiber-enhanced STicking (NEST) method. In this example, a nanofiber sheet (e.g., bacterial cellulose) is attached to a surface (e.g., a porous substrate, such as porous titanium) with an adhesive (e.g., α-TCP cement), after which a hydrogel component is infiltrated into the nanofiber sheet.
[0047] Figure 1B An example of a hydrogel bonded to a titanium plug is shown.
[0048] Figure 1C Shown is a SEM image of the surface of an exemplary freeze-dried bacterial cellulose sheet.
[0049] Figure 2A-2D Various hydrogel samples are shown before and after annealing and rehydration to illustrate the effect on the morphology of different hydrogel compositions.
[0050] Figure 3A-3E is a graph illustrating the effect of annealing on the mechanical properties of various hydrogel compositions: Figure 3A The figure shows the tensile stress-strain curves of PVA hydrogels annealed at different temperatures; Figure 3B The figure shows the compressive stress-strain curves of PVA hydrogels annealed at different temperatures; Figure 3C The graph shows the tensile strength and modulus of PVA annealed at different temperatures; Figure 3D The graph shows the compressive stress and modulus at 0.8 strain for PVA annealed at different temperatures; and Figure 3E The graph shows the crystallinity and solid content weight fraction of PVA annealed at different temperatures.
[0051] Figure 4A-4E is a graph illustrating the effect of annealing on the mechanical properties of BC-PVA hydrogels. Figure 4A The figure shows the tensile stress-strain curves of BC-PVA hydrogels annealed at different temperatures; Figure 4B The figure shows the compressive stress-strain curves of BC-PVA hydrogels annealed at different temperatures; Figure 4CThe graph shows the tensile strength and modulus of BC-PVA annealed at different temperatures; Figure 4D The graph shows the compressive stress and modulus at 0.8 strain of BC-PVA annealed at different temperatures; and Figure 4E The graph shows the crystallinity and solid content weight fraction of BC-PVA annealed at different temperatures.
[0052] Figure 5A and Figure 5B is a graph illustrating the effect of PAMPS on annealed BC-PVA hydrogel: Figure 5A The graph shows the tensile strength, tensile modulus, and solid content weight fraction of BC-PVA-PAMPS hydrogels prepared from solutions containing different concentrations of AMPS monomer, wherein the BC-PVA samples were annealed prior to AMPS infiltration; and Figure 5B The graph shows the compressive strength and modulus of BC-PVA-PAMPS hydrogels.
[0053] Figure 6A-6D The graph shows aspects of measuring the wear and coefficient of friction (COF) of various hydrogel compositions and comparing such measurements to cartilage: Fig. 6A Schematic diagram showing how to measure the wear and COF of a hydrogel relative to cartilage; Figure 6B Figure shows micro-CT cross-sectional images of cartilage and hydrogel samples; Figure 6C The graph shows the wear depth of cartilage and hydrogel samples after 106 cycles at 1 MPa pressure, 100 mm / s rotation rate, and FBS as lubricant; and Fig.6D The graph shows the COF between cartilage and hydrogel during the testing period of 24 hours.
[0054] Figure 7A-7C The figures show aspects of measuring the wear of various hydrogel compositions and comparing such measurements to cartilage: Fig. 7A A schematic diagram illustrating how the wear of cartilage relative to a hydrogel is measured; Figure 7B The figure shows a micro-CT cross-sectional image; and Figure 7C The graph shows the wear depth of cartilage and hydrogel samples after 106 cycles at 1 MPa pressure, 100 mm / s rotation rate, and FBS as lubricant.
[0055] Figure 8A-8D Figures show aspects of shear strength testing of various hydrogel compositions and cartilage: Fig. 8A Figure shows the results of shear testing of porcine cartilage and hydrogel secured to a metal pin using an adhesive and a shape memory alloy fixture; Figure 8BThe figure shows an image of an osteochondral column extracted from a pig knee after testing to failure; Figure 8C shows an image of a BC-PVA-PAMPS hydrogel (made using a freeze-thaw process) after testing to failure; and Fig.8D Shown are images of BC-PVA hydrogels (fabricated by annealing at 90°C and rehydrating) after testing to failure.
[0056] Figure 9A-9F Shown are front and side views of an annealed BC-PVA hydrogel incorporated into an implant for partial knee resurfacing before and after being subjected to mechanical stress.
[0057] Fig. 10A and Fig. 10B Schematic diagrams illustrate embodiments of implants including a hydrogel attached (eg, forming a surface) as described herein.
[0058] Fig.11 An exemplary method of forming and attaching a hydrogel surface is shown.
[0059] Fig. 12A is an image illustrating one embodiment of a method of attaching a hydrogel to a metal pillar, the method including using a clamp (eg, a shape memory alloy clamp).
[0060] Fig. 12B and Fig. 12C Figures illustrate embodiments of fixtures (e.g., alignment BCs, including rods, cut BCs, and ring fixtures) that may be used to align materials formed as described herein, as described herein: Fig. 12B showing a perspective view of the fixing device; and Fig. 12C A cross-section through the fixture is shown.
[0061] Fig.12D is an image showing an exemplary bacterial cellulose (BC) sheet cut (eg, with legs or serrations) for wrapping around the edge of a support surface (eg, a metal rod, a head, etc.).
[0062] Fig.12E is a diagram indicating the diameter D dimension, length L dimension, and width W dimension of one embodiment of a sheet.
[0063] Fig.13 is an embodiment of a test fixture that can be used to test shearing of cartilage from bone and / or shearing of hydrogel material from a test rod.
[0064] FIG. 14A shows an example of a process for attaching a BC-PVA-PAMPS hydrogel to a titanium implant for treating osteochondral defects.
[0065] 14B and 14C show the repair of the implant.
[0066] Figures 15A-15D show hydrogel samples before and after annealing and rehydration. All samples were annealed at 90°C for 25 hours and rehydrated in PBS solution at 23°C for 24 hours. (A) BC sample without PVA. (B) BC sample annealed in a solution of 10 wt.% PVA. (C) Sample with 40 wt.% PVA. (D) BC sample infiltrated with 40 wt.% PVA in a hydrothermal bomb at 120°C for 24 hours before annealing and rehydration.
[0067] FIG. 16A shows FTIR spectra of BC-PVA, annealed BC-PVA, and annealed PVA hydrogels.
[0068] Figure 16B shows a magnified region highlighting the shift in the hydroxyl peak. Figure 16A shows the increase in hydrogen bonding that occurs upon annealing.
[0069] Figure 17A-17C DSC thermograms of (A) freeze-thawed and annealed PVA hydrogel, (B) freeze-thawed and annealed BC-PVA hydrogel, and (C) annealed BC-PVA and annealed BC-PVA-PAMPS are shown. The concentration of the AMPS solution used to prepare BC-PVA-PAMPS was 10 wt.%.
[0070] Fig.18 Shown is the DSC thermogram of an annealed BC-PVA hydrogel sample, demonstrating how the peaks are integrated. Details
[0071] The hydrogel composition for the long-term repair of cartilage is described herein.Hydrogel has a crystalline structure, and the tensile strength and compressive strength of the crystalline structure imparting the hydrogel are equal to or exceed the tensile strength and compressive strength of the cartilage.Hydrogel can be incorporated into a nanofiber network (e.g., cellulose) to increase wear properties and / or promote attachment to an implant body.Hydrogel has been found to be able to withstand high compressive stress and shear stress associated with the motion of the knee joint, and is therefore very suitable for implementation on knee implants.Hydrogel can be characterized by one or more attributes and properties, such as crystalline structure, tensile strength, compressive strength, water content, coefficient of friction (COF) and / or other attributes and properties.
[0072] The methods of forming hydrogel implants described herein can be used to produce hydrogel-coated orthopedic implants having surfaces that simulate or improve the mechanical and / or tribological properties of cartilage. Methods of forming implants having hydrogels comprising a bacterial cellulose (BC) network infused with polyvinyl alcohol (PVA) and poly(2-acrylamido-2-methyl-1-propanesulfonic acid sodium salt) (PAMPS), referred to as BC-PVA-PAMPS hydrogels, were previously described in International Patent Application No. PCT / US2021 / 040031, which is incorporated herein by reference in its entirety. When preparing the BC-PVA-PAMPS hydrogel, a freeze-thaw method is used to gel the PVA-water mixture after infiltration into the BC. The freeze-thaw gelation step is used to increase the strength of the PVA hydrogel and prevent the PVA from dissolving in the subsequent PAMPS infiltration step. The increase in strength when the PVA is frozen and thawed is attributed to the crystallization and phase separation of the PVA chains.
[0073] Method described herein improves these previous methods by improving the mechanical properties of the hydrogel that strengthens, thereby improves the performance of implant, even when subjected to high impact force and shearing force.For example, the tensile strength and compressive strength of the hydrogel that strengthens can increase until and exceed the tensile strength and compressive strength of cartilage.These methods relate to mechanical strengthening process, and this mechanical strengthening process increases the crystallinity of PVA and reduces the water content of PVA relative to freeze-thaw process.Mechanical strengthening process can comprise drying, annealing and / or rehydration of hydrogel.When implementing on hydrogel, the crystalline structure in hydrogel can increase, although be mutually interlaced in fiber network.In addition, hydrogel can be substantially bubble-free and crack-free after experiencing crystal reconstruction process.
[0074] Figure 1A-Figure 1C The embodiment of the equipment that hydrogel has been attached to the implant surface as described herein is illustrated.Hydrogel can be connected to the implant surface by first using adhesive (for example cement) that nanofiber material such as cellulose (for example bacterial cellulose) layer is attached to the implant base.Nanofiber material can be dry (for example, before being attached to the implant base).The attachment surface of implant base can be porous, for example, to enhance adhesion.Then the nanofiber layer can be infiltrated with hydrogel component.In this way, the nanofiber part can be fixed by adhesive (for example, cement), and the adhesive can infiltrate the porous bacterial cellulose network and be fixed to the surface, and can produce the interlaced joint when there is no water interference.Once the hydrogel component is infiltrated in the nanofiber network, the enhanced hydrogel can be processed (for example, annealing) to change the crystalline structure of the hydrogel component, thereby improving the mechanical properties of the enhanced hydrogel.
[0075] For example, in Figure 1A In the embodiment, the nanofiber part is bacterial cellulose (BC) 101, which is applied to the prepared surface of the implant (shown as a titanium base with holes in this embodiment) 103. A cement is applied (for example, any suitable medical or dental grade cement can be used), and the dried bacterial cellulose is fixed to the implant surface. Thereafter, the hydrogel component can penetrate into the nanofiber part, resulting in a complete hydrogel 107 attached to the base 103 via the bacterial cellulose 101. The enhanced hydrogel 107 then undergoes a crystal reorganization process to improve its mechanical properties.
[0076] Figure 1B The embodiment of the titanium implant (for example, column) to which the hydrogel enhanced by cellulose is attached is shown, as described herein.In this embodiment, the nanofiber part (for example BC) of hydrogel is bonded to the porous surface of implant via adhesive, and hydrogel is connected to the nanofiber part.Any suitable adhesive (for example, cement) can be used to adhere the nanofiber part of hydrogel to the surface of implant.In some modifications, cement is α-tricalcium phosphate (α-TCP), a cement forming hydroxyapatite, because the biocompatibility, osteoconductivity and shear strength of α-TCP may exceed the biocompatibility, osteoconductivity and shear strength of cyanoacrylate, so α-TCP can be used for the attachment of hydrogel.In some cases, α-TCP is combined with phosphoserine (PPS) to promote adhesion.In some cases, hydroxyapatite is strengthened with stainless steel powder (SSP) (for example, with an average particle size of 150 μm) to hinder crack propagation. As will be described in more detail below, in some embodiments, no adhesive is used and the nanofiber portion is secured to the support surface by mechanical means, such as a clamp.
[0077] As described herein, the nanofiber portion (eg, BC) can be treated to be dried (eg, freeze-dried) to increase adhesion to the nanofibers. Figure 1C is a scanning electron microscope (SEM) image of the surface of an exemplary freeze-dried BC sheet, which shows that the BC sheet is composed of many nanoscale fibers that present a large surface area for attachment with an adhesive. In some embodiments, multiple freeze-thaw cycles are performed, which can increase the tensile strength (once the hydrogel is injected therein) and / or increase the shear strength of the adhesion of the enhanced hydrogel to the implant base.
[0078] As mentioned above, previous methods for producing cartilage-equivalent hydrogels involve infiltrating bacterial cellulose (BC) nanofiber networks with polyvinyl alcohol (PVA) and poly(2-acrylamido-2-methyl-1-propanesulfonic acid sodium salt) (PAMPS). The hydrogel exhibited a tensile strength of 22.6 MPa and a compressive strength of 20 MPa. In comparison, the ranges of tensile and compressive strengths reported for human cartilage are 8.1 MPa-40 MPa and 14 MPa-59 MPa, respectively. Therefore, there is room to increase the strength of the hydrogel to the high end of the strength range reported for cartilage, or to exceed cartilage in strength while having a modulus, friction coefficient, and wear resistance similar to that of cartilage. Given that annealed PVA has a higher tensile strength relative to freeze-thawed PVA, tests were conducted to determine whether changing from a freeze-thaw process to an annealed process could improve the mechanical strength of the BC-PVA-PAMPS hydrogel while maintaining adequate control over the hydrogel shape and defect content. Given that the tensile strength of the BC-PVA-PAMPS hydrogels (22.6 MPa) is already similar to that of PVA hydrogels prepared by annealing (20 MPa), it is not obvious that switching to an annealing process for the BC-reinforced hydrogels would produce additional improvements in mechanical strength. Furthermore, the presence of BC or PAMPS could potentially interfere with the crystallization of PVA that occurs during the annealing process, thereby hindering the improvement in mechanical strength that occurs as a result of crystallization. It is also unclear whether it is possible to obtain high-quality, bubble-free, crack-free samples after annealing PVA reinforced with BC. Obtaining samples that are as defect-free as possible may be necessary to maximize the mechanical strength of the hydrogels. Finally, it is unclear whether the lower water content of the annealed hydrogels could result in excessively high COFs and relative surface wear.
[0079] As demonstrated herein, reinforcing annealed PVA with BC resulted in a 3.2-fold improvement in tensile strength (from 15.6 MPa to 50.5 MPa) and a 1.7-fold increase in compressive strength (from 56.7 MPa to 95.4 MPa). The highly crystallized BC-PVA hydrogel produced by annealing is the first hydrogel with tensile and compressive strengths that exceed those of cartilage. Reinforcing PVA with BC can substantially eliminate deformation and bubbles that would otherwise occur during annealing. When tested against cartilage, annealed BC-PVA wears the relative cartilage surface to the same extent as cartilage, and has three times the wear resistance of cartilage. The COF of BC-PVA to cartilage is comparable to that of cartilage to cartilage. In contrast to the results of freeze-thawed BC-PVA, adding PAMPS to annealed BC-PVA reduces the tensile strength of the hydrogel due to the loss of crystallized PVA and the increase in water content. The improved tensile strength of annealed BC-PVA enables it to be attached to a metal base with a shear strength that is 68% higher than the shear strength of cartilage to bone. The high strength, high wear resistance and low COF of annealed BC-PVA make it an excellent material for replacing damaged cartilage.
[0080] The tests and measurements performed and described herein on a variety of hydrogel compositions demonstrate how certain hydrogel compositions that undergo one or more strengthening processes, such as an annealing process, can increase the strength of the hydrogel to or beyond the upper limit of cartilage while achieving other properties (e.g., coefficient of friction) that are similar to those of cartilage.
[0081] A potential disadvantage of annealing hydrogels is that the hydrogels may develop bubbles and cracks, especially as the sample thickness increases or the water content increases. Figure 2A-2D Various hydrogel samples before and after annealing and rehydration are shown to illustrate the effect on the morphology of different hydrogel compositions. In particular, these samples illustrate the effect of the hydrogel composition on the shape of the sample after drying, annealing, and rehydration. All samples were annealed at 90°C for 25 hours and rehydrated at 23°C in phosphate buffered saline (PBS) solution for 24 hours. Figure 2A Shown is a BC sample (without PVA), demonstrating how the BC sample becomes wrinkled and folded at the edges after annealing and rehydration. Figure 2B BC samples annealed in a solution of 10 wt.% PVA are shown. As shown, BC annealed in a 10 wt.% PVA solution also exhibits significant deformation. The PVA layer formed on top of the BC after annealing contains a large amount of bubbles and is easily delaminated from the BC film. The bubbles may be the result of water evaporation. Figure 2D Sample 40 wt.% PVA is shown before and after annealing, demonstrating that such hydrogels also form a large number of bubbles and deform during the annealing process.
[0082] FIG. 2E shows a BC sample infiltrated with 40 wt.% PVA in a hydrothermal bomb at 120° C. for 24 hours prior to annealing and rehydration. As shown, reinforcing the 40 wt.% PVA with BC allows the hydrogel to retain its shape with little deformation after annealing. This lack of deformation can be attributed to the higher solids content and tensile modulus of the BC-reinforced PVA. That is, the nanoscale network of the BC layer appears to suppress the formation of large bubbles visible in the 40 wt.% PVA sample ( Figure 2C ). Figure 2B and Figure 2D A comparison of the results showed that the method of infiltrating high concentrations of PVA into BC in a hydrothermal bomb followed by removal of excess PVA from the BC surface resulted in a more uniform hydrogel than if the BC sample was placed in a more dilute PVA solution (concentrated by drying). These results demonstrate that, unlike BC alone, PVA alone, or a combination of BC and 10 wt.% PVA, BC infiltrated with 40 wt.% PVA can retain its shape after annealing and remain relatively free of bubbles and other defects.
[0083] Figure 3A-3E The effect of annealing on the mechanical properties of various hydrogel compositions is shown, with the effect of annealing on PVA hydrogels analyzed as a reference point. PVA is fully hydrolyzed and has a molecular weight of 145,000 g mol -1 40 wt.% PVA solutions were dried at 90°C for 24 hours, annealed at 90°C, 120°C, or 140°C, and then placed in 0.15 M PBS solution for 24 hours for rehydration. PVA samples that underwent freeze-thaw cycles were tested for comparison. Figure 3A and Figure 3B It was shown that annealing the hydrogels significantly increased the tensile and compressive strengths relative to samples that had undergone freeze-thaw cycles. Figure 3C and Figure 3DIt is shown that annealing increases the tensile strength by 60 times (from 0.26 MPa to 15.6 MPa) and the compressive strength by 9 times (from 14.8 MPa to 140.8 MPa) relative to the freeze-thaw process. Increasing the annealing temperature from 90°C to 140°C leads to an increase in tensile strength and modulus. The increase in strength and modulus is attributed to the increase in the crystallinity and solid content of the hydrogel after annealing. FIG2E confirms that the crystallinity and solid content of the annealed PVA hydrogel are much greater than those of the frozen-thawed PVA hydrogel. For example, the PVA hydrogel prepared via the freeze-thaw process has a total solid content of 0.09 and a PVA crystallinity of 0.21, while the PVA hydrogel prepared via annealing at 90°C has a total solid content of 0.42 and a PVA crystallinity of 0.58. The crystallites formed during annealing strengthen the otherwise amorphous PVA by acting as tough cross-linking portions, which redistribute the applied stress and hinder crack propagation. The microcrystals also increased the solid content and strength of the hydrogel by reducing the amount of water absorbed by the PVA after annealing when it was soaked in 0.15 M PBS.
[0084] Figure 4A-4E The figure shows the effect of annealing on BC-PVA hydrogel. Figure 3A-3E The same annealing process described for PVA hydrogels was applied to BC-PVA hydrogels. As with PVA hydrogels, BC-PVA hydrogels were dried at 90°C for 24 hours, annealed at 90°C, 120°C, or 140°C, and then placed in 0.15 M PBS solution for 24 hours for rehydration. Figure 4A and Figure 4C The tensile strength of the annealed BC-PVA hydrogel was shown to reach 50.4 MPa, a 4.6-fold increase relative to BC-PVA subjected to freeze-thaw cycles and a 3.2-fold increase relative to annealed PVA without BC reinforcement. Figure 4B and Figure 4D It is shown that the compressive strength increases from 55.32 MPa to 95.35 MPa after annealing. Similar to the PVA hydrogel, this significant increase in strength can be attributed to the increase in crystallinity and solid content after annealing. Figure 3E The crystallinity of the BC-PVA hydrogel was shown to increase from 0.07 after freeze-thaw cycles to 0.4 after annealing. The solid weight fraction of the BC-PVA hydrogel increased from 0.11 after freeze-thaw cycles to 0.53 after annealing. These results indicate that PVA can still form crystallites within the nanofiber BC network, and these crystallites increase the solid content and strength of the hydrogel.
[0085] Figure 5A and Figure 5BThe figure shows the effect of PAMPS on annealed BC-PVA hydrogels. As mentioned above, it was previously found that incorporating PAMPS into BC-PVA hydrogels prepared using freeze-thaw cycles resulted in an increase in the tensile and compressive strength of the hydrogels. Therefore, PAMPS was incorporated into annealed BC-PVA hydrogels to determine the effect of adding PAMPS. Figure 5A As shown in , the addition of PAMPS to the annealed BC-PVA hydrogel resulted in a decrease in solid content from 0.53 to 0.37 relative to BC-PVA alone. The differential scanning calorimetry (DSC) thermogram showed that the peak from the melted crystalline PVA disappeared after the addition of 10 wt.% PAMPS, indicating that the addition of PAMPS destroyed the PVA crystallites formed during the annealing process. The decrease in solid content and loss of crystallinity after the addition of PAMPS resulted in an increase in the tensile strength (from 48.9 MPa to 20.8 MPa), tensile modulus (from 444.8 MPa to 150.5 MPa), and compressive strength (in Figure 5B The increase in water content of the hydrogel and the loss of strength may be due to the fact that PAMPS are negatively charged polymers and this negative charge causes an osmotic pressure that causes the hydrogel to swell with water.
[0086] Figure 6A-6D The figures show aspects of measuring the wear and coefficient of friction (COF) of various hydrogel compositions and comparing such measurements to cartilage. Fig. 6A Schematic diagram of an example of how the wear test was performed. The pin-on-disc configuration described in Example 11 below for testing the wear of the hydrogel in fetal bovine serum (FBS) was used. The porcine cartilage column was subjected to a pressure of 1 MPa and a speed of 319 revolutions per minute (maximum linear speed of 100 mm s -1 ) were rotated 106 times relative to the hydrogel surface. The wear resistance of the potential replacement for cartilage exceeds that of cartilage to ensure durability and minimize the generation of wear debris that could cause adverse biological reactions. The wear resistance of BC-PVA-PAMPS hydrogels was previously shown to be comparable to that of cartilage and superior to that of PVA or PVA-PAMPS when tested against a stainless steel pin. These hydrogels were prepared by applying freeze-thaw cycles to crystallize the PVA. Figure 6B-6D The wear resistance of PVA-based hydrogels (PVA, BC-PVA, and BC-PVA-PAMPS) that had been dried and annealed at 90°C was compared to the wear resistance of porcine cartilage when tested on porcine cartilage cylinders in FBS.
[0087] Figure 6BShown are cross-sectional micro-CT images of the hydrogel taken at the center of the wear mark to measure the maximum wear depth. Figure 6C The wear depth of the hydrogel and cartilage were compared. The wear depth of the BC-PVA hydrogel with 0% AMPS was 70.1 μm. Adding 20% AMPS reduced the average wear depth to 65.9 μm, but the difference between the 0% AMPS sample and the 20% AMPS sample was not statistically significant. This comparison shows that the negative charge and higher water content caused by incorporating PAMPS into the annealed BC-PVA hydrogel do not significantly improve the wear resistance. Both values are one-third of the wear depth (227.8 μm) on the cartilage sample. The wear depth of the annealed and rehydrated PVA is 301.0 μm, which is four times that of any BC-PVA sample. These results indicate that the presence of BC in the hydrogel can significantly improve the wear resistance of the annealed PVA hydrogel to be better than the wear resistance of cartilage.
[0088] The COF was recorded during the wear test, as Fig.6D . During the test, the cartilage maintained a constant COF of 0.020. During the test, the COF of BC-PVA decreased from 0.040 to 0.021. The BC-PVA hydrogel with 20% AMPS has a COF similar to that of the BC-PVA hydrogel without AMPS. In contrast, the COF of PVA increased significantly from 0.033 to 0.135 during the test. Previous work similarly demonstrated that the COF of PVA to cartilage increased over time, while the COF of cartilage to cartilage was constant. The increase in COF for the PVA-cartilage interface is attributed to the transfer of damaged PVA to the cartilage surface, which in turn reduces the ability of the cartilage surface to maintain a lubricating water layer. The incorporation of BC into PVA significantly inhibits damage to the hydrogel, allowing it to maintain a low coefficient of friction similar to that of cartilage during wear testing. The presence of AMPS in the hydrogel does not appear to be necessary for maintaining a low COF and high wear resistance.
[0089] The material used for cartilage replacement on one side of the joint, i.e., the femoral condyle, should not cause wear of the cartilage on the opposite surface, i.e., the tibial plateau. Traditional orthopedic materials such as cobalt-chromium and ultra-high molecular weight polyethylene are known to damage the opposite cartilage surface to a greater extent than hydrogels due to their higher COF and hardness. In order to evaluate the wear of cartilage caused by BC-PVA hydrogel and BC-PVA-PAMPS hydrogel, hydrogel columns were produced for wear testing (see Example 7 below). The hydrogel columns were pressed onto the cartilage samples at a pressure of 1 MPa (see Example 7 below). Fig. 7A ) and rotated 106 times at a speed of 319 revolutions per minute (maximum linear speed on the periphery of the pin was 100 mm s -1).
[0090] Figure 7B Shown are cross-sectional micro-CT images of cartilage samples taken at the center of the wear mark to measure the maximum wear depth. Figure 7C The depth of wear on cartilage caused by hydrogel or cartilage was compared. The wear caused by BC-PVA on cartilage (247 μm ± 16 μm) was not significantly different from the wear caused by cartilage on cartilage (228 μm ± 12 μm). Adding PAMPS to BC-PVA reduced the wear on the opposing cartilage surface to 81 μm ± 27 μm, which is significantly lower than the wear of cartilage on cartilage.
[0091] Figure 8A-8D Aspects of shear strength testing of various hydrogel compositions and cartilage are shown. It is assumed that increasing the tensile strength of the hydrogel will also increase the shear strength. In order to be used for cartilage replacement materials, synthetic hydrogels should be fixed to the defect site with the same shear strength as the connection between cartilage and bone. One way to achieve this goal is to have a hydrogel that is directly attached to the bone or cartilage with sufficient strength. Alternatively, the hydrogel can be attached to a metal base, such as titanium, that has the ability to integrate with the bone. As mentioned above, the BC-PVA-PAMPS hydrogel can be attached to a metal base with a shear strength equivalent to the shear strength of the cartilage-bone interface, as described in PCT / US2021 / 040031. Previous tests have shown that the strength of the hydrogel attachment is limited by the tension required to break the hydrogel bent on the edge of the metal base. Therefore, increasing the tensile strength of the hydrogel will increase the shear strength used by the hydrogel to attach to the metal base.
[0092] The setup for shear testing is described in Examples 7 and 12 below. Figure 8A-8DResults are shown for shear testing of columns of porcine cartilage on bone extracted from a porcine knee, testing of BC-PVA-PAMPS hydrogels prepared with a previous freeze-thaw process, and testing of BC-PVA hydrogels annealed at 90°C and then rehydrated. Both hydrogels were attached to a stainless steel rod using a combination of RelyX Ultimate cement and a shape memory alloy ring. The BC-PVA shear strength of 1.98 was significantly greater than that of porcine cartilage (p-value <0.05 for one-way ANOVA). The mean value of the shear strength of BC-PVA was also 40% greater than that of BC-PVA-PAMPS, but the error in the measurements made the difference in these values not statistically significant. Comparison of the samples after failure shows that both BC-PVA-PAMPS (prepared with a freeze-thaw process) and BC-PVA (prepared by annealing at 90°C followed by rehydration) broke on one side of the cylindrical sample, but remained attached, when the porcine cartilage was completely sheared off the underlying bone. These results indicate that the shear strength of the attachment of annealed BC-PVA is greater than that of porcine cartilage.
[0093] The tensile, compressive, and shear strengths of BC-enhanced hydrogels attached to a 5.2 mm diameter metal pin are described above. While this size is convenient for testing, such a diameter is too small to be used as an implant for partial knee resurfacing. In addition, the sample lacks the curvature required to simulate the natural curvature of the femoral condyle. Figure 9A-9F The annealed BC-PVA hydrogel was shown applied to an implant for partial knee resurfacing to demonstrate the ability of the hydrogel to attach to a metal base having a size and shape representative of an implant for partial knee resurfacing.
[0094] Fig.9A and Fig. 9B The implant is shown before mechanical testing. The diameter of the implant sample is 20 mm and the radius of curvature is 20 mm. The implant diameter of 20 mm is a typical size for allogeneic osteochondral grafts, and the radius of curvature of 20 mm is within the range of the typical curvature of the femoral condyle. For a body weight of 100 kg, the peak force on the knee during jogging was measured to be 5551 N. The tibiofemoral contact area has been measured to be 1500 mm at 3100 N. 2 Based on the assumption that the contact area does not increase at higher forces, the peak stress on the contact area of the knee during jogging was 3.7 MPa. Fig. 9C and Fig.9DImplant after being subjected to 16 MPa of compressive stress is shown, and this compressive stress is 4.3 times of peak physiological force (peak physiological force) on femoral condyle.After this test, there is no sign of fracture or damage on the surface of hydrogel.This test shows that the implant made of annealed BC-PVA hydrogel can withstand the compression force in knee and can not fracture.The peak anterior shear force (peakanterior shear force) in knee when walking has been measured to be 30% of body weight, or 294 N for the individuality of 100 kg.This is the highest shear force measured in knee in the daily activities of any research.The tibia contact area has been measured to be 1500mm when 3100 N. 2 , which is approximately equivalent to the peak normal force during walking for an individual weighing 100 kg. Since the peak normal force coincides with the peak shear force, we can use this tibiofemoral contact area to calculate that the peak shear stress experienced by the cartilage during walking is 0.2 MPa (294 N ÷ 1500 mm 2 ). Shear testing of the implants showed that failure did not occur until a stress of 0.9 MPa was applied. Since the implants could withstand shear loads 4.5 times that experienced by cartilage in the knee, this result suggests that the annealed BC-PVA hydrogel and the method of attachment have sufficient strength to produce an implant for partial knee resurfacing.
[0095] The implant for partial knee resurfacing can be relatively large and can be bent to simulate the natural curvature of the femoral condyle. Figure 14A-Figure 14C shows an image of an implant with a diameter of 20 mm and a radius of curvature of 20 mm. The implant diameter of 20 mm is the typical size for allogeneic osteochondral grafts, and the radius of curvature of 20 mm is within the range of the typical curvature of the femoral condyle. In this embodiment, five pieces of BC are cut into a shape with 8 octagonal legs so that BC can be folded on the edge of the implant. A coating of commercially pure titanium of 0.25 mm thick is applied to the stem and base of the implant below the plasma spraying process to improve integration with bone. Figure 14B and Figure 14C show an embodiment of how such an implant will be used to resurface the knee. Figure 14B shows an embodiment of cartilage defects. The surgeon will drill a hole at the defect site that is complementary to the shape of the implant covered with hydrogel. The implant covered with hydrogel will then be pressed into the hole to replace the damaged cartilage.
[0096] Method and apparatus described herein can be used to strengthen annealed PVA hydrogel with BC, to provide hydrogel with compression strength and tensile strength greater than cartilage for the first time.Relative to freeze-thaw process, annealing increases the tensile strength of BC-PVA by 5 times and increases the compressive strength by 1.8 times, and this is because annealing realizes larger crystallinity and lower water content.Relative to independent PVA, strengthen PVA with BC and reduce the wear of hydrogel to one-quarter times, reduce to one-third times relative to cartilage.Annealed BC-PVA hydrogel causes the wear of relative surface minimum amount, and this is similar to the wear caused by cartilage to itself.BC is attached to metal column via adhesive and / or clamp, followed by infiltration and annealing of PVA, so that BC-PVA hydrogel can be attached to metal backing (metal backing) with the shear strength greater than the attachment of cartilage to bone.These advances in hydrogel strength and attachment make it possible to produce implants with hydrogel surface and titanium backing, which can realize the durable surface repair of damaged cartilage in articulating joint (articulating joint).
[0097] As used herein, implants can have any suitable structure for implantation in the body. In some (non-limiting) embodiments, implants can have a shape that allows them to be implanted in the bone, with the hydrogel attached to the side facing outward. For example, Fig. 10A and Fig. 10B The figure shows an embodiment of an implant to which a hydrogel has been attached, as described herein. Fig. 10A In, the implant includes a base 1001 (e.g., a titanium base) having an elongated pin shape, which can be, for example, 2 mm × 7 mm (tapering to about 1.5 mm at about 3 mm from the end). The base can include one or more channels, openings, passages, etc. for bone ingrowth. The implant also includes a top portion 1005 that can be curved (e.g., having a single curvature or a double curvature). For example, the surface can be curved with a radius of curvature of about 17 mm (single curvature) or about 19 mm × 12 mm (double curvature). In Fig. 10A In the embodiment, the diameter of the top 1007 is about 7 mm. The outer surface 1009 of the implant can be about 1 mm thick or thicker, and can be about 70% or more porous. The hydrogel can be attached to the top surface. The hydrogel in this embodiment is a triple network hydrogel of BC-PVA-PAMPS, and the BC is cemented to the porous top, while the PVA-PAMPS is impregnated into the BC. Fig. 10B Shown with Fig. 10A An implant similar to the implant shown in , in which a hydrogel is attached (e.g., by bonding the nanofiber portion of the hydrogel to the porous surface of the implant, as shown). Fig. 10B The implants in are titanium.
[0098] As mentioned above, any one of these implant surfaces can comprise porous structure.The porosity of implant surface can be for example between 10% porosity and 90% porosity, for example between 30% porosity and 90% porosity, between 55% porosity and 95% porosity, between 65% porosity and 85% porosity, etc.The degree of depth in hole also can change.For example, the surface can be porous to between 0.1 mm and 5 mm, between 0.2 mm to 3 mm, between 0.5 mm to 2 mm (for example, 0.2 mm or larger, 0.3 mm or larger, 0.5 mm or larger, 0.75 mm or larger, 1 mm or larger, 1.5 mm or larger, etc.) degree of depth.
[0099] As mentioned, any suitable nanofiber network can be used, including but not limited to nanofiber bacterial cellulose. Other nanofiber networks can include electrospun polymer nanofibers such as poly(vinyl alcohol) (PVA) nanofibers, aromatic polyamide nanofibers (e.g., aromatic polyamide-PVA nanofibers), wet-spun protein nanofibers, chemically cross-linked cellulose nanofibers, or polycaprolactone fibers (e.g., 3D woven PCL fibers). In addition, any suitable double network hydrogel can be used, including but not limited to PVA and PAMPS. For example, other hydrogel-forming polymers may include poly(N,N'-dimethylacrylamide) (PDMAAm), copolymers of 1-vinylimidazole and methacrylic acid, double network hydrogels based on amphiphilic triblock copolymers, polyampholyte hydrogels, PVA-tannic acid hydrogels, poly(N-acryloyl)glycinamide hydrogels, polyacrylic acid-acrylamide-C18 hydrogels, guanine-boronic acid-enhanced PDMAAm, polyelectrolyte hydrogels, poly(acrylonitrile-co-l-vinylimidazole) hydrogels (e.g., mineralized poly(acrylonitrile-co-l-vinylimidazole) hydrogels), polyacrylic acid-Fe hydrogels. 3+ -Chitosan hydrogel, poly(methacrylic acid) gel, graphene oxide / xenotime reinforced polyacrylamide (PAAm) gel, poly(stearyl methacrylate)-polyacrylic acid gel, annealed PVA-polyacrylic acid hydrogel, supramolecular hydrogel from copolymers of polyurea chain segments, polyacrylonitrile-PAAm hydrogel, microsilica reinforced DMA gel, agar-poly(hydroxyethyl methacrylate) gel, polyacryloylethyltrimethylammonium chloride hydrogel, poly(3-methacrylamido)propyl-trimethylammonium chloride hydrogel, poly(sodium p-styrene sulfonate) hydrogel, polyethylene glycol diacrylate hydrogel, polyethylene glycol hydrogel, or a hydrogel comprising a combination of these polymers.
[0100] Implant described herein can be formed by any suitable material, and described material includes but is not limited to titanium and stainless steel.For example, as described herein, hydrogel can be attached to the implant surface (for example, base, including porous base) formed by the following items: stainless steel alloy, other titanium alloys, Co-Cr alloy, tantalum, gold, niobium, bone, Al oxide, Zr oxide, hydroxyapatite, tricalcium phosphate, sodium calcium phosphosilicate (bioglass (Bio glass)), poly (methyl methacrylate), polyetheretherketone, polyethylene, polyamide, polyurethane, polytetrafluoroethylene, or other materials for making implant.
[0101] Any implant described herein can include a hydrogel having a surface that is substantially smooth and / or shaped in a predetermined configuration, such as, but not limited to, concave, convex, saddle-shaped, etc. For example, any of these devices (e.g., implants) can have a surface roughness less than 30 microns. In some cases, the surface can be formed to be smooth by molding. In some cases, the surface can be formed to be smooth by polishing or sanding. For example, once the additional hydrogel components have formed a network (e.g., a nanofiber-reinforced network), the hydrogel coating can be optionally completed by polishing; in particular, the surface can be sanded to be polished to a roughness less than 30 microns. Polishing can be performed by sanding (e.g., using a fine-grained sanding surface, such as 600, 400, 320, etc.).
[0102] Fig.11 1101 is a flow chart illustrating an exemplary method of manufacturing a device as described herein. The surface 1101 to which the hydrogel is to be attached can be optionally prepared, such as an implant surface. For example, the surface can be made porous. In some embodiments, the porosity can be at least 0.5 mm deep (e.g., 1 mm deep or deeper). The porosity can be described as a percentage porosity (e.g., between 10% porosity and 90% porosity, between 20% porosity and 90% porosity, greater than 30% porosity, greater than 40% porosity, greater than 50% porosity, etc.).
[0103] The nanofiber portion can then be prepared for attachment to a surface 1103. For example, the nanofiber portion is dried (e.g., freeze dried). The nanofiber portion can be applied dry or substantially dry to an attachment surface 1105. The nanofiber portion can then be fixed to a surface 1107. In some variations, an adhesive (e.g., a cement) can be applied to the surface before applying the nanofiber portion and / or an adhesive can be applied to the nanofiber portion on the surface. In some variations, an adhesive can be applied to the nanofiber portion before attaching to a surface. In some embodiments, no adhesive is used at all.
[0104] The adhesive, if used, can be applied to dry (e.g., for a predetermined time, such as 1 hour, 2 hours, 3 hours, 6 hours, 12 hours, 24 hours, etc.) at a drying temperature (e.g., room temperature, 30 degrees, etc.). Once dried, the nanofiber portion bonded to the surface can optionally be rehydrated 1109, such as by adding an aqueous solution.
[0105] The nanofiber portion can then be infiltrated by other components of the hydrogel, which become impregnated into the nanofiber portion fixed to the surface 1111. The other components may include one or more polymer components that can form a hydrogel and are crystallizable during a subsequent annealing process. In some embodiments, the polymer component includes polyvinyl alcohol (PVA). In some embodiments, the polymer component includes only PVA.
[0106] Once the polymer hydrogel component is injected into the nanofiber portion, a mechanical strengthening process can be implemented to strengthen the hydrogel. The mechanical strengthening process can include drying, annealing and rehydration of the hydrogel. Drying and / or annealing can include heating the hydrogel to a predetermined temperature (e.g., ranging from 90° C. to 140° C.), followed by rehydration (e.g., in a PBS solution). The resulting hydrogel can have an increased crystalline structure. For example, a gap polymer hydrogel (e.g., PVA) can have a crystallinity of at least 20%. In some embodiments, the tensile strength of the resulting hydrogel is at least 40 MPa. In some embodiments, the compressive strength of the resulting hydrogel is at least 59 MPa. In addition, the hydrogel can have a water content of about 20 wt.% or more. Once the mechanical strengthening process is completed, the hydrogel surface can be optionally polished 1115.
[0107] In some embodiments, the devices described herein can form part of a surgical implant for treating defects such as osteochondral defects. For example, a surgical implant can include a surface covered in a hydrogel; the surface can act as an interface between one or more other body regions, including hard tissues, such as bone and cartilage. Repairing cartilage damage with hydrogels can benefit from the long-term fixation of the hydrogel in the defect site. Attaching the hydrogel to a base (substrate) that allows integration with the bone can achieve long-term fixation of the hydrogel, but the current method of forming a bond with the hydrogel has a shear strength of less than one-tenth of the shear strength of the osteochondral connection. The devices and methods described herein can include bonding the hydrogel to a surface (e.g., a base) with a shear strength many times greater than the shear strength previously obtained.
[0108] Figure 12A-12CThe figure shows a brief overview of an embodiment of how a hydrogel can be attached to a metal base (e.g., the metal base of a top bearing surface). In this embodiment, a freeze-dried BC sheet is cut into an octagonal shape with 8 protrusions (e.g., "legs") that can be bent over the edge of the implant, such as Fig.12D This cutting removes excess BC that would otherwise be folded over the sides of the cylinder. The cut BC piece is then placed in a fixture, which aids in centering and aligning the ring fixture with the BC piece and the metal bar. The metal bar is pushed down through the fixture so that the ring pushes the BC piece onto the metal bar. This process of pushing the ring onto the BC and onto the bar can also be done by hand. Figure 12B-Figure 12C The use of the alignment features shown in can help to consistently center the sheet during assembly. The sample can then be clamped, for example, by heating in an oven at 90°C to begin clamping in a pre-set shape memory alloy material as described herein (which starts at a temperature of 50°C). The part is then heated in a hydrothermal bomb at 120°C for 24 hours with PVA to infiltrate the polymer into the BC. The part is then dried, annealed, and rehydrated as described herein.
[0109] The following are exemplary methods for preparing and testing the various hydrogel samples described herein.
[0110] Example 1: Preparation of BC-PVA-PAMPS hydrogel The BC sheet is pressed into 0.5 mm thick and placed in a hydrothermal reactor with a mixture of polyvinyl alcohol (PVA) (40 wt.%) and deionized water (60 wt.%). The hydrothermal reactor is sealed and heated at 120 ° C for 24 hours to allow PVA to diffuse into the gaps of BC and form a BC-PVA hydrogel. When hot (e.g., greater than 85 ° C), the BC-PVA hydrogel is removed from the reactor. Residual PVA solution is removed by scraping the surface of the BC-PVA sample with a metal scraper. The sample is frozen at -78 ° C for 30 minutes and melted at room temperature to physically crosslink the PVA network. Then, the BC-PVA hydrogel was immersed in 2-acrylamido-2-methylpropanesulfonic acid sodium salt (AMPS) (30 wt.%), N,N'-methylenebisacrylamide (MBAA) (60 mM), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (I2959) (50 mM), and potassium persulfate (KPS) (0.5 mg mL -1) solution for 24 hours. The hydrogel was cured on each side with an ultraviolet (UV) transilluminator for 15 minutes and further cured in an oven at 60°C for 8 hours to ensure uniform and complete curing. The resulting BC-PVA-PAMPS hydrogel was stored in phosphate buffered saline (PBS) for at least 24 hours before further characterization.
[0111] Example 2: Preparation of annealed BC The BC sheet was pressed to 0.5 mm thickness. The BC sheet was then placed in an oven at 90°C for 24 hours and then annealed at 90°C for another hour. The resulting annealed BC was cut into desired shapes and stored in 0.15 M PBS for at least 24 hours.
[0112] Example 3: Preparation of PVA hydrogel To prepare PVA hydrogels, a slurry of PVA (40 wt.%) and deionized water (60 wt.%) was mixed in a metal baking pan (diameter: 203.2 mm) and heated at 120°C for 20 minutes in an autoclave sterilizer. To prepare annealed PVA hydrogels, the resulting hydrogels were dried in an oven at 90°C for 24 hours and then annealed at 90°C, 120°C, or 140°C for another hour. To prepare freeze-thawed PVA hydrogels, the autoclaved hydrogels were frozen at -80°C for 30 minutes and melted at 23°C for 30 minutes. The resulting PVA hydrogels were cut into desired shapes and stored in 0.15 M PBS for at least 24 hours before testing.
[0113] Example 4: Preparation of Annealed BC-40 wt.% PVA Hydrogel BC sheet is pressed into 0.5 mm thick, and put into hydrothermal reactor together with the mixture of PVA (40 wt.%) and deionized water (60 wt.%). Hydrothermal reactor is sealed and heated at 120 ° C for 24 hours to allow PVA to diffuse into the gap of BC and form BC-PVA hydrogel. When hot (for example, greater than 85 ° C), BC-PVA hydrogel is removed from reactor. Note that hydrothermal reactor is pressurized with hot steam, and causes burn risk (burn hazard), so personal protective equipment should be used when opening the reactor, and personal protective equipment includes lab coat, heat-resistant gloves and full-coverage face shield (full-coverage face shield). Residual PVA solution is removed by scraping the surface of BC-PVA sample with a metal scraper. Sample is dried in an oven at 90 ° C for 24 hours, then annealed at 90 ° C, 120 ° C or 140 ° C for another hour. The resulting annealed BC-PVA hydrogels were cut into desired shapes and stored in 0.15 M PBS for at least 24 hours before testing.
[0114] Example 5: Preparation of Annealed BC-10 wt.% PVA Hydrogel The BC sheet was pressed into 0.5 mm thickness and placed in a baking tray (15.6 cm × 8.6 cm × 4.2 cm). About 30 mL of 10 wt.% PVA solution was added to the baking tray. The baking tray was placed in an oven at 90°C for 24 hours and annealed at 90°C for another hour. The resulting annealed BC-PVA hydrogel was cut into desired shapes and stored in 0.15 M PBS for at least 24 hours.
[0115] Example 6: Preparation of Annealed BC-PVA-PAMPS Hydrogel BC sheet is pressed into 0.5 mm thick, and put into hydrothermal reactor together with the mixture of PVA (40 wt.%) and deionized water (60 wt.%). Hydrothermal reactor is sealed and heated at 120 ° C for 24 hours, to allow PVA to diffuse into the void of BC and form BC-PVA hydrogel. When hot (>85 ° C), BC-PVA hydrogel is removed from reactor. Note that hydrothermal reactor is pressurized with hot steam, and causes burn risk, so personal protective equipment should be used when opening reactor, and personal protective equipment includes lab coat, heat-resistant gloves and full coverage mask. Residual PVA solution is removed by scraping the surface of BC-PVA sample with a metal scraper. Sample is dried in an oven at 90 ° C for 24 hours, then annealed at 90 ° C, 120 ° C or 140 ° C for another hour. The annealed BC-PVA hydrogel was then immersed in AMPS (30 wt.%), MBAA (60 mM), I2959 (50 mM), and KPS (0.5 mg mL -1 ) solution for 24 hours. The hydrogels were cured on each side with a UV transilluminator (VWR International) for 15 minutes and further cured in an oven at 60°C for 8 hours to ensure uniform and complete curing. The resulting annealed BC-PVA-PAMPS hydrogels were stored in PBS for at least 24 hours before further characterization.
[0116] Example 7: Preparation of hydrogel on stainless steel pins The preparation of all hydrogel samples began with cutting of freeze-dried BC. BC was cut into an octagonal shape with a diameter D and 8 legs with a leg length of L and a width of W = 0.383D (see e.g. Figure 2A-2D ). After cutting, the sample is marked as BC-DL. 8 star shapes (BC-DL) are produced by MATLAB and loaded into Adobe Illustrator. In Adobe Illustrator, the stroke of the shape is changed to 0.0001 ft to ensure accurate cutting. The file is sent to a laser cutter (laser cutter) (Epilog FusionM2) by using the print function, and the laser cutter is selected as a printer. Vector process was used, using 100% speed, 20% power and 100% frequency. In order to cut BC, a clean metal plate is placed on the bed of the laser cutter, and freeze-dried BC is placed on the metal plate. Another metal plate is placed on the edge of BC to ensure that BC remains in place. Focus was adjusted, and the shape was cut by the machine. After cutting, BC was collected and stored in a culture dish for future use.
[0117] To prepare the shear test specimens, six pieces of BC were adhered to a stainless steel bar using a layer of cement and a clamp. An overview of the assembly method is shown in Figure 12A-12C and Fig.13 In. The stainless steel test rod is processed into a top portion with a diameter of 5.2 mm and a height of 2 mm and a bottom portion with a diameter of 6.75 mm and a height of 13 mm. 3 pieces of BC-6.5-2.25 and 3 pieces of BC-6.5-2 are placed in an alignment fixture. As an optional step, an adhesive (such as Scotchbond universal adhesive) can be applied to the layer of BC in contact with the top surface of the rod and the rod. If used, the adhesive is allowed to solidify for 20 seconds and then blown with air for another 5 seconds. Then, in one embodiment, about 0.15 g of RelyX Ultimate adhesive is applied to the same surface coated with Scotchbond universal adhesive. The rod is pressed into the BC layer and then pressed into the shape memory alloy ring fixture. The adhesive is cured for 1 hour. The sample is heated in an oven at 175°C for 10 minutes to shrink the fixture. Then before future use, the sample is soaked in deionized water in a centrifuge tube for 1 hour. Then, the samples with BC on top underwent a specific hydrogel fabrication process.
[0118] Compression test specimens were prepared using a stainless steel bar and fixture but without cement. Wear test specimens were prepared using a stainless steel bar with a diameter of 5.7 mm and a height of 38 mm, 3 pieces of BC-6.5-2 and a shape memory alloy ring but without cement.
[0119] Example 8: Monotonic Tensile and Compression Test The samples were loaded on Instron 1321 (Instron, Norwood, MA, USA) and TestResources 830 (TestResources, Shakopee, MN, USA) load frames at 0.25 mm s -1The monotonic tensile test was performed at a rate of . The completed hydrogel was cut into an ASTM D638-14 V-shape for testing with a titanium hollow punch (see, e.g., FIG. 1 ). Prior to testing, the dimensions of the sample were measured with a caliper. The ultimate tensile strength (UTS) is the maximum stress measured before fracture in the case of BC-PVA samples, or the maximum compressive stress at 80% strain for PVA samples. The tensile modulus is taken as the slope of the stress-strain curve at a stress of 1 MPa for comparison with previous studies on human cartilage.
[0120] The compression properties of all samples were measured using an axial torsion system (TestResources 830LE63). A cylindrical sample of PVA was cut from the hydrogel film with a hollow steel punch of 4 mm in diameter. The BC-PVA sample was attached to a metal pin for compression testing in order to have a sufficiently thick sample. Prior to testing, the size of the sample was measured with a caliper. The sample was tested using a 0.05 s -1 The compressive properties were measured at strain rates of 1.5 Å. The ultimate compressive strength was taken as the maximum stress measured before fracture. The compressive modulus was derived as the slope of the stress-strain curve at a stress of 0.4 MPa for comparison with previous studies on human cartilage.
[0121] Example 9: Differential Scanning Calorimetry Differential scanning calorimetry (DSC) was performed on the hydrogels to determine the crystallinity of PVA. The tests were performed on a TA TGA550. In a typical experiment, approximately 5 mg of the hydrogel sample was placed in an aluminum pan under a nitrogen stream and heated from 25°C to 300°C at a rate of 10°C / min. Typical thermograms of PVA, BC-PVA, and BC-PVA-PAMPS hydrogels are shown in Figure 4A-4D Shown in.
[0122] The calculation of how much PVA is crystallized, i.e., the degree of crystallinity, is taken from Hassan et al. 22. After obtaining the DSC thermogram, the area under the melting peak in the range of 140°C to 220°C (e.g., Figure 5A and Figure 5B The unit is J·℃·S -1 ·g -1 Then divide this value by the heating rate (0.17℃·S -1 ) to obtain ΔH (J·g -1 ). The ΔH of the sample is then divided by the heat required to melt a 100% crystalline PVA sample, ΔH e =138.6 J / g and the weight fraction of PVA in the sample W PVA, to calculate the crystallinity of PVA,
[0123]
[0124] where χ PVA is the crystallinity of PVA.
[0125] Example 10: Measurement of solid weight fraction The weight of about 1 g of hydrated hydrogel was measured before drying at 90°C for 24 hours. The weight of the dehydrated sample was then measured. The weight after dehydration was divided by the weight before dehydration to determine the solid weight fraction of the hydrogel sample.
[0126] Example 11: Wear test The wear resistance of hydrogel and porcine cartilage samples was tested by Figure 6A-6D The pin-on-disk apparatus shown in was measured. The pin-on-disk method was used with an Anton Paar rheometer (MR302) and a tribology accessory (SCF7). Cartilage samples were collected from porcine femurs using an osteochondral autograft transfer system (Arthrex). Femurs were purchased from local grocery stores and frozen at -78°C before collecting samples. Prior to testing, the hydrogel samples were polished with #600, #800, #1000, #1200, #1500, #2000, #2500 and #3000 sandpaper to make them smooth. The hydrogel pins were made by using the method described in Example 7 above. A disc of hydrogel or porcine cartilage with a diameter of 12.7 mm was adhered to the sample holder with cyanoacrylate glue (Gorilla Glue Company). The test parameters are as follows: 1,000,000 rotations; angular velocity: 319 revolutions per minute (maximum linear velocity: 100 mm s -1 ); Normal force: 28.26 N (pressure: 1 MPa). Before the test started, a pressure of 1 MPa was applied to each sample for 5 minutes. The test was carried out in FBS. FBS is usually used during wear testing to simulate the lubrication provided by synovial fluid.
[0127] After the wear test, the samples were rehydrated in FBS for 24 hours to allow the gel to recover from the applied pressure, and then the wear depth was measured with a high-resolution X-ray computed tomography (micro-CT) scanner (Nikon XTH 225 ST). The 3D model of the reconstructed micro-CT image was rendered with Avizo 9 Lite. To measure the wear depth, a slice of the 3D model was taken in the middle of the wear mark. The wear depth was measured from the image of the slice in the middle using ImageJ.
[0128] To calculate COF, we determine the total friction force (F) based on the torque (T) and the radius of the pin in the pin-on-disk arrangement (R): .
[0129] The COF can then be calculated as follows: .
[0130] Here, F N is the normal force (28.26 N). The linear velocity (v) is calculated by:
[0131]
[0132] where ω is the angular velocity of the pin.
[0133] The results described above are particularly and unexpectedly surprising, indicating that the annealed BC-PVA as described herein provides a material that maintains a low coefficient of friction (0.21) in 1 million or more wear cycles, which is similar to the coefficient of friction of cartilage (0.2). In contrast, the COF of the annealed PVA itself increases from 0.033 to 0.135 in the million cycles. It is particularly surprising that adding BC to PVA results in a long-term COF that is 6.5 times the COF of the PVA itself. This lower COF achieved by BC is crucial for preventing wear on the relative cartilage surface. Similarly, it is surprising that, relative to a single annealed PVA, adding BC to the annealed PVA reduces the wear depth by more than three times. This greater wear resistance achieved by BC may also be crucial for the long-term durability of the implant.
[0134] Example 12: Shear Test Shear tests were performed on an 830LE63 axial torsion testing machine equipped with a 100 lb load cell. Each test was performed in a custom shear test fixture (see Fig.13 ). To shear cartilage or hydrogel on metal samples, the sample is secured in a cylindrical hole on the left side of the fixture. For porcine cylinders, the hole diameter is 6 mm and for hydrogel samples, the hole diameter is 7 mm. Spacers are added underneath the sample to precisely align the shear plane with the cartilage-bone or hydrogel-metal interface. The right side of the fixture is machined with complementary half cylinders that are used to push the hydrogel or cartilage away from their substrates. The diameter of the right half cylinder matches that of the left side (6 mm or 7 mm). Rubber is placed between the sample and the right side shear fixture to apply pressure during the shear test to minimize cracking and delamination. A 2 mm min.-1 The crosshead displacement rate.
[0135] Supplementary Materials As mentioned, in some of these examples, bacterial cellulose (BC) was purchased from Gia Gia Nguyen Co. Ltd. Poly(vinyl alcohol) (PVA) (fully hydrolyzed, molecular weight: 145,000 g mol -1 ), N, N'-methylenebisacrylamide (MBAA, 97.0%), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (I2959), potassium persulfate (KPS) and 2-acrylamido-2-methylpropanesulfonic acid sodium salt (AMPS, 50 wt.% aqueous solution) were purchased from Sigma Aldrich. Phosphate buffered saline (PBS) was purchased from VWR International. Fetal bovine serum (FBS, Canadian source, collected from cattle usually 12-24 months old) was purchased from Corning. Shape memory alloy ring fixture was purchased from Intrinsic Devices.
[0136] In some embodiments, the BC sheet is pressed into a thickness of 0.5 mm and placed in a hydrothermal reactor with a mixture of PVA (40 wt.%) and deionized water (60 wt.%). The hydrothermal reactor is sealed and heated at 135 ° C for 24 hours to allow PVA to diffuse into the voids of BC and form BC-PVA hydrogel. When hot (> 85 ° C), the BC-PVA hydrogel is removed from the reactor. Note that the hydrothermal reactor is pressurized with hot steam and there is a risk of burns, so personal protective equipment should be used when opening the reactor, including lab coats, heat-resistant gloves and full-coverage masks. The residual PVA solution is removed by scraping the surface of the BC-PVA sample with a metal scraper. The sample was frozen at -78 ° C for 30 minutes and thawed at room temperature to physically crosslink the PVA network. The BC-PVA hydrogel was then soaked in AMPS (30 wt.%), MBAA (60mM), I2959 (50 mM) and KPS (0.5 mg mL -1 ) solution for 24 hours. The hydrogels were cured on each side with a UV transilluminator (VWR International) for 15 minutes and further cured in an oven at 60°C for 8 hours to ensure uniform and complete curing. The resulting BC-PVA-PAMPS hydrogels were stored in PBS for at least 24 hours before further characterization.
[0137] As mentioned, the BC sheet is pressed to, for example, about 0.5 mm thick. Then, in some embodiments, the BC sheet is placed in an oven at 90° C. for 24 hours and then annealed at 90° C. for another hour. The resulting annealed BC is cut into desired shapes and stored in PBS (0.15 M) for at least 24 hours.
[0138] Any suitable method can be used to prepare PVA hydrogel.For example, in order to prepare PVA hydrogel, a slurry of PVA (40 wt.%) and deionized water (60 wt.%) is mixed in a metal baking pan (diameter: 203.2 mm) and heated at 120°C for 20 minutes in an autoclave. In order to prepare annealed PVA hydrogel, the resulting hydrogel is dried in an oven at 90°C for 24 hours, then annealed at 90°C, 120°C or 140°C for another hour. In order to prepare the PVA hydrogel of freeze-thaw, the autoclaved hydrogel is frozen at -80°C for 30 minutes, and melted at 23°C for 30 minutes. The resulting PVA hydrogel is cut into desired shapes, and stored in PBS (0.15 M) for at least 24 hours before testing.
[0139] Annealed BC-40 wt.% PVA hydrogel can be prepared in any suitable manner.For example, the BC sheet can be pressed into 0.5 mm thick and put into a hydrothermal reactor together with a mixture of PVA (40 wt.%) and deionized water (60 wt.%). The hydrothermal reactor is sealed and heated at 135 ° C for 24 hours to allow PVA to diffuse into the gap of BC and form a BC-PVA hydrogel. When hot (>85 ° C), the BC-PVA hydrogel is removed from the reactor. The residual PVA solution is removed by scraping the surface of the BC-PVA sample with a metal scraper. The sample is dried in an oven at 90 ° C for 24 hours, and then annealed at 90 ° C, 120 ° C or 140 ° C for another hour. The annealed BC-PVA hydrogel obtained is cut into a desired shape, and stored in PBS (0.15 M) for at least 24 hours before testing.
[0140] In some embodiments, annealed BC-10 wt.% PVA hydrogels are prepared by pressing BC sheets to about 0.5 mm thick and placing them into baking trays (15.6 cm × 8.6 cm × 4.2 cm). About 30 mL of 10 wt.% PVA solution is added to the baking tray. The baking tray is placed in an oven at 90°C for 24 hours and annealed at 90°C for another hour. The resulting annealed BC-PVA hydrogels are cut into desired shapes and stored in PBS (0.15 M) for at least 24 hours.
[0141] Annealed BC-PVA-PAMPS hydrogels were prepared by pressing BC sheets to about 0.5 mm thick and placed in a hydrothermal reactor with a mixture of PVA (40 wt.%) and deionized water (60 wt.%). The hydrothermal reactor was sealed and heated at 120°C for 24 hours to allow PVA to diffuse into the voids of BC and form BC-PVA hydrogels. When hot (>85°C), the BC-PVA hydrogel was removed from the reactor. Note that the hydrothermal reactor is pressurized with hot steam and causes a risk of burns, so personal protective equipment should be used when opening the reactor, including lab coats, heat-resistant gloves, and full-coverage masks. Residual PVA solution was removed by scraping the surface of the BC-PVA sample with a metal scraper. The samples were dried in an oven at 90°C for 24 hours and then annealed at 90°C, 120°C, or 140°C for another hour. The annealed BC-PVA hydrogel was then immersed in AMPS (30 wt.%), MBAA (60 mM), I2959 (50 mM), and KPS (0.5 mg mL -1 ) solution for 24 hours. The hydrogel was cured on each side with a UV transilluminator (VWR International) for 15 minutes and further cured in an oven at 60°C for 8 hours to ensure uniform and complete curing. The resulting annealed BC-PVA-PAMPS hydrogel was stored in PBS (0.15 M) for at least 24 hours before further characterization.
[0142] Preparation of hydrogels on stainless steel pins In certain embodiments, hydrogel samples are prepared on stainless steel pins to start with cutting freeze-dried BC. BC is cut into an octagonal shape with diameter D, 8 legs, and the legs have a length of L and a width of W=0.383D. After cutting, the sample is labeled BC-DL. 8 star shapes (BC-DL) are generated by MATLAB and loaded into Adobe Illustrator. In Adobe Illustrator, the stroke of the shape is changed to 0.0001 ft to ensure accurate cutting. The file is sent to a laser cutter (Epilog Fusion M2) using the print function, and the laser cutter is selected as a printer. A vector process was used, using 100% speed, 20% power and 100% frequency. In order to cut BC, a clean metal plate is placed on the bed of the laser cutter, and freeze-dried BC is placed on the metal plate. Another metal plate is placed on the edge of BC to ensure that BC does not move. The focus is adjusted, and the shape is cut by the machine. After cutting, BC is collected and stored in a culture dish for future use.
[0143] To prepare the shear test specimens, six pieces of BC were adhered to a stainless steel rod with a layer of adhesive and a fixture. The stainless steel test rod was machined to have a top portion with a diameter of 5.2 mm and a height of 2 mm and a bottom portion with a diameter of 6.75 mm and a height of 13 mm. Three pieces of BC-6.5-2.25 and three pieces of BC-6.5-2 were placed in an alignment fixture. Scotchbond universal adhesive was applied to the BC layer in contact with the top surface of the rod and the rod. The adhesive was allowed to solidify for 20 seconds and then blown with air for another 5 seconds. Then, about 0.15 g of RelyX Ultimate adhesive was applied to the same surface coated with Scotchbond universal adhesive. The rod was pressed into the BC layer and then pressed into the shape memory alloy ring fixture. The adhesive was cured for 1 hour. The sample was heated in an oven at 175°C for 10 minutes to shrink the fixture. The sample was then soaked in deionized water in a centrifuge tube for 1 hour before future use. Then, the samples with BC on top underwent a specific hydrogel fabrication process.
[0144] Compression test specimens were prepared using a stainless steel bar and fixture but without cement. Wear test specimens were prepared using a stainless steel bar with a diameter of 5.7 mm and a height of 38 mm, 3 pieces of BC-6.5-2 and a shape memory alloy ring but without cement.
[0145] The loads were measured on an Instron 1321 load frame (Instron, Norwood, MA, USA) and a Test Resources 830LE63 axial-torsion tester (Test Resources, Shakopee, MN, USA) at 0.25 mm s -1 The monotonic tensile test was performed at a rate of . The completed hydrogel was cut into an ASTM D638-14 V-shape for testing with a titanium hollow punch (see, e.g., Figures 15A-15D). Prior to testing, the dimensions of the sample were measured with a caliper. The ultimate tensile strength (UTS) is the maximum stress measured before fracture in the case of BC-PVA samples, or the maximum compressive stress at 80% strain for PVA samples. The tensile modulus is taken as the slope of the stress-strain curve at a stress of 1 MPa for comparison with previous studies on human cartilage.
[0146] The compressive properties of all samples were measured using a Test Resources 830LE63 axial torsion testing machine. Cylindrical samples of PVA were cut from the hydrogel sample films using a hollow steel punch with a diameter of 4 mm. The BC-PVA samples were attached to metal pins for compression testing in order to have sufficiently thick samples. Prior to testing, the dimensions of the samples were measured using a caliper. A 0.05s -1 The compressive properties were measured at a strain rate of 1.5 Å. The compressive strength was taken as the stress at a strain of 0.8, or the stress at rupture if the material failed before a strain of 0.8. The compressive modulus was derived as the slope of the stress-strain curve at a stress of 0.4 MPa for comparison with previous studies on human cartilage.
[0147] Differential scanning calorimetry (DSC) was performed on the hydrogel samples to determine the crystallinity of PVA. The tests were performed on a TA Instruments TGA550. In a typical test, approximately 5 mg of the hydrogel sample was placed in an aluminum pan and heated from 25°C to 300°C under a nitrogen flow at a scan rate of 10°C / min. Typical thermograms of PVA, BC-PVA, and BC-PVA-PAMPS hydrogels are shown in Figure 17A-17C Shown in.
[0148] A calculation of how much PVA is crystallized, i.e., the degree of crystallinity, was performed. After obtaining the DSC thermogram, the area under the melting peak in the range of 140°C to 220°C (e.g., Fig.18 The unit is J·℃·S -1 ·g -1 Then divide this value by the heating rate (0.17℃·S -1 ) to obtain ΔH (J·g -1 ). The ΔH of the sample is then divided by the heat required to melt a 100% crystalline PVA sample (ΔH c =138.6 J / g) and the weight fraction of PVA in the sample W PVA , to calculate the crystallinity of PVA (X PVA ):
[0149] .
[0150] The weight of about 1 g of hydrated hydrogel was measured before drying at 90°C for 24 hours. The weight of the dehydrated sample was then measured. The weight after dehydration was divided by the weight before dehydration to determine the solid weight fraction of the hydrogel sample.
[0151] Fourier transform infrared (FTIR) spectroscopy was performed on the hydrogel samples to analyze changes in binding after annealing. Prior to testing, the hydrogel samples were cut into 1 cm by 1 cm squares. Testing was done on a Thermo Scientific NicoletiS50 FT-IR. In a typical test, the sample was held under the detector with the number of scans set to 32 and the resolution set to 4 (0.482 cm -1 ) and the format is set to % Transmittance. Typical FTIR spectra are shown in Figures 16A-16B.
[0152] The wear resistance of hydrogel and porcine cartilage samples was determined using a pin-on-disk apparatus. The pin-on-disk method was used with an Anton Paar rheometer (MR302) and a tribology accessory (SCF7). Cartilage samples were collected from porcine femurs using an osteochondral autograft transfer system (Arthrex). Femurs were purchased from local grocery stores and frozen at -78°C before collecting samples. Prior to testing, the hydrogel samples were polished with #600, #800, #1000, #1200, #1500, #2000, #2500, and #3000 sandpaper to make them smooth. The hydrogel pins were made using the method described in Section 2.8. A disc of hydrogel or porcine cartilage with a diameter of 12.7 mm was adhered to the sample holder with cyanoacrylate glue (Gorilla Glue Company). The test parameters were as follows: 1,000,000 rotations; angular velocity: 319 revolutions per minute (maximum linear velocity: 100 mm s -1 ); Normal force: 28.26 N (pressure: 1 MPa). Before starting the test, a pressure of 1 MPa was applied to each sample for 5 minutes. The test was performed in FBS. FBS is usually used during wear testing to simulate the lubrication provided by synovial fluid.
[0153] After the wear test, the samples were rehydrated in FBS for 24 hours to allow the gel to recover from the applied pressure, and then the wear depth was measured with a high-resolution X-ray computed tomography (micro-CT) scanner (Nikon XTH 225 ST). The 3D model of the reconstructed micro-CT image was rendered with Avizo 9 Lite. To measure the wear depth, a slice of the 3D model was taken in the middle of the wear mark. The wear depth was measured from the image of the slice in the middle using ImageJ.
[0154] To calculate COF, we determine the total friction force (F) based on the torque (T) and the radius of the pin in the pin-on-disk arrangement (R): .
[0155] The COF can then be calculated as follows: .
[0156] Here, F N is the normal force (28.26 N). The linear velocity (v) is calculated by:
[0157]
[0158] where ω is the angular velocity of the pin.
[0159] Shear tests were performed on a Test Resources 830LE63 axial-torsion test machine equipped with a 100 lb load cell. Each test was performed in a custom shear test fixture (see Fig.13 ). To shear cartilage from bone or hydrogel from metal specimens, the specimen is secured in a cylindrical hole on the left side of the fixture. Spacers are added beneath the specimen to precisely align the shear plane with the cartilage-bone or hydrogel-metal interface. The right side of the fixture is machined with complementary half-cylinders that are used to push the hydrogel or cartilage away from their substrate. A rubber spacer is placed between the specimen and the right side shear fixture to apply pressure during shear testing to minimize cracking and debonding. A 2 mm min. -1 The crosshead displacement rate.
[0160] A human-sized osteochondral implant with a diameter of 20 mm was prepared. The top surface of the implant had a radius of curvature of 20 mm to match the natural curvature of the femoral condyle. The implant was made of 5 BC layers. A 0.25 mm thick coating of commercially pure titanium was applied to the stem and base of the implant under a plasma spray process to improve integration with the bone.
[0161]
[0162] The table above shows the mechanical properties of annealed BC-PVA, annealed BC-PVA-PAMPS, annealed PVA hydrogels, cartilage, and previously reported hydrogels. The table compares the properties of annealed BC-PVA with freeze-thawed hydrogels and other previous hydrogels, showing significant improvements in properties.
[0163] Abbreviations used in this table: BC: bacterial cellulose; PVA: poly(vinyl alcohol); PAMPS: poly(2-acrylamido-2-methyl-1-propanesulfonic acid sodium salt); PAAm: polyacrylamide; CNC: cellulose nanocrystals; PA: phenyl acrylate; HA: hydroxyapatite; HACC: 2-hydroxypropyltrimethylammonium chloride chitosan; PCL: polycaprolactone; CS: chitosan. For clarity, the references in this table are limited to publications that report all four metrics, strength and modulus in tension and compression, and where the tensile strength and compressive strength are above 3 MPa.
[0164] Any method described herein (including user interfaces) may be implemented in software, hardware, or firmware, and may be described as a non-transitory computer-readable storage medium storing a set of instructions executable by a processor (e.g., a computer, tablet, smartphone, etc.), which, when executed by the processor, causes the processor to control the execution of any steps, including but not limited to: display, communication with a user, analysis, modification of parameters (including timing, frequency, intensity, etc.), determination, alarm, etc.
[0165] It should be appreciated that all combinations of the foregoing concepts and additional concepts discussed in greater detail below (provided such concepts are not mutually inconsistent) are contemplated as being part of the inventive subject matter disclosed herein and can be used to achieve the benefits described herein.
[0166] When a feature or element is referred to as "on another feature or element" in this article, it can be directly on another feature or element, or there can also be intermediate features and / or elements. In contrast, when a feature or element is referred to as "directly on another feature or element", there are no intermediate features or elements. It will also be understood that when a feature or element is referred to as "connected", "attached" or "coupled" to another feature or element, it can be directly connected, attached or coupled to another feature or element, or there can be intermediate features or elements. In contrast, when a feature or element is referred to as "directly connected", "directly attached" or "directly coupled" to another feature or element, there are no intermediate features or elements. Although described or shown for one embodiment, the features and elements described or shown in this way can be applied to other embodiments. It will also be understood by those skilled in the art that when referring to a structure or feature "adjacent" another feature setting, the structure or feature can have a portion overlapping or located under an adjacent feature with an adjacent feature.
[0167] The terms used herein are only used for the purpose of describing specific embodiments, and are not intended to limit the present invention. For example, unless the context clearly indicates otherwise, as used herein, the singular forms "a", "an", and "the" are intended to also include the plural forms. It will also be understood that the terms "comprises" and / or "comprising" when used in this specification specify the presence of stated features, steps, operations, elements, and / or parts, but do not exclude the presence or addition of one or more other features, steps, operations, elements, parts, and / or groups thereof. As used herein, the term "and / or" includes any and all combinations of one or more of the related listed items, and may be abbreviated as " / ".
[0168] For ease of description, spatially relative terms such as "below", "below", "lower", "above", "upper", etc. may be used herein to describe the relationship of one element or feature to another element or feature, as illustrated in the accompanying drawings. It will be understood that, in addition to the orientation depicted in the accompanying drawings, spatially relative terms are intended to cover different orientations of the device in use or operation. For example, if the device in the accompanying drawings is inverted, then the elements described as "below" or "below" other elements or features will then be oriented "above" other elements or features. Therefore, the exemplary term "below" can cover both upper and lower orientations. The device can be oriented in other ways (rotated 90 degrees or in other orientations), and the spatially relative descriptors used herein are interpreted accordingly. Similarly, unless otherwise specifically stated, the terms "upward", "downward", "vertical", "horizontal", etc. are used herein only for the purpose of explanation.
[0169] Although the terms "first" and "second" may be used herein to describe a variety of features / elements (including steps), these features / elements should not be limited by these terms unless the context indicates otherwise. These terms may be used to distinguish one feature / element from another feature / element. Therefore, without departing from the teachings of the present invention, the first feature / first element discussed below may be referred to as the second feature / second element, and similarly, the second feature / second element discussed below may be referred to as the first feature / first element.
[0170] Throughout this specification and the appended claims, unless the context requires otherwise, the word "comprise" and variations, such as "comprises" and "comprising" mean that various components can be used together in methods and articles (e.g., compositions and devices including apparatus and methods). For example, the term "comprising" will be understood to imply the inclusion of any stated elements or steps but not the exclusion of any other elements or steps.
[0171] Generally, any apparatus and method described herein should be understood to be inclusive, but all or a subset of components and / or steps may optionally be exclusive and may be expressed as "consisting of a variety of components, steps, sub-components or sub-steps" or optionally "consisting essentially of a variety of components, steps, sub-components or sub-steps."
[0172] As used in the specification and claims, including as used in the embodiments and unless otherwise expressly provided, all numbers can be understood to start with the word "about" or "approximately", even if the term does not clearly appear.When describing magnitude and / or position, the phrase "about" or "approximately" can be used to represent that the value and / or position described are within the reasonable expected range of value and / or position.For example, numerical value can have the value of + / - 0.1% of the stated value (or range of value), + / - 1% of the stated value (or range of value), + / - 2% of the stated value (or range of value), + / - 5% of the stated value (or range of value), + / - 10% of the stated value (or range of value), etc. Any numerical value given herein should also be understood to include about or about the value, unless otherwise specified in context.For example, if the value "10" is disclosed, then "about 10" is also disclosed.Any numerical range listed herein is intended to include all subranges contained therein. It should also be understood that when a value is disclosed, "less than or equal to" the value, "greater than or equal to the value," and possible ranges between values are also disclosed, as appropriately understood by those skilled in the art. For example, if a value "X" is disclosed, "less than or equal to X" and "greater than or equal to X" (e.g., where X is a numerical value) are also disclosed. It should also be understood that throughout the application, data is provided in a variety of different formats, and that the data represents endpoints and starting points, as well as ranges for any combination of data points. For example, if a specific data point "10" and a specific data point "15" are disclosed, it should be understood that greater than 10 and greater than 15, greater than or equal to 10 and greater than or equal to 15, less than 10 and less than 15, less than or equal to 10 and less than or equal to 15, and equal to 10 and equal to 15, and between 10 and 15 are considered disclosed. It should also be understood that every unit between two specific units is also disclosed. For example, if 10 and 15 are disclosed, 11, 12, 13, and 14 are also disclosed.
[0173] Although various illustrative embodiments are described above, any of a variety of changes may be made to the various embodiments without departing from the scope of the invention as described by the claims. For example, in selectable embodiments, the order in which the various described method steps are performed can often be changed, and in other selectable embodiments, one or more method steps may be skipped together. The optional features of the various device and system embodiments may be included in some embodiments but not in other embodiments. Therefore, the foregoing description is provided primarily for exemplary purposes and should not be construed as limiting the scope of the invention as set forth in the claims.
[0174] The embodiments and diagrams included herein illustrate the specific embodiments that can implement the theme by way of illustration and not limitation. As mentioned, other embodiments can be utilized and derived therefrom, so that structural replacement and change and logical replacement and change can be performed without departing from the scope of the present disclosure. Such embodiments of the subject matter of the present invention can be referred to individually or collectively by the term "invention" herein, which is merely for convenience, and is not intended to voluntarily limit the scope of the present application to any single invention or inventive concept, if in fact more than one invention or inventive concept is disclosed. Therefore, although specific embodiments have been shown and described herein, any arrangement that plans to achieve the same purpose can replace the specific embodiments shown. The present disclosure is intended to cover any and all modifications or changes of a variety of embodiments. After reading the above description, the combination of the above embodiments and other embodiments that are not specifically described herein will be obvious to those skilled in the art.
Claims
1. An implant comprising: an implant body having a top bearing surface; Anchor base; as well as A cellulose-reinforced hydrogel comprising: a cross-linked cellulose nanofiber network affixed to the top bearing surface of the implant body; and An interstitial hydrogel portion within the interstitial regions of the cross-linked cellulose nanofiber network, wherein the interstitial hydrogel portion has a crystallinity of 20% or greater.
2. The implant of claim 1, wherein the interstitial hydrogel portion comprises polyvinyl alcohol (PVA).
3. The implant of claim 1, wherein the cellulose-reinforced hydrogel comprises at least 20% water by weight.
4. The implant of claim 1, wherein the cellulose reinforced hydrogel has a tensile strength exceeding 40 MPa.
5. The implant of claim 1, wherein the cross-linked cellulose nanofiber network is chemically cross-linked.
6. The implant of claim 1, wherein the cross-linked cellulose nanofiber network comprises bacterial cellulose.
7. The implant of claim 1, wherein the cellulose reinforced hydrogel has a compressive strength exceeding 59 MPa.
8. The implant of claim 1, wherein the cross-linked cellulose nanofiber network is secured to the top support surface by a clamp.
9. An implant according to claim 8, wherein the cross-linked cellulose nanofiber network comprises one or more bacterial cellulose (BC) sheets, and the one or more bacterial cellulose sheets are retained on the top support surface by a clamp fixed to a lip or edge of the top support surface.
10. A method of forming an implant having a cellulose reinforced hydrogel, comprising: attaching a cross-linked cellulose nanofiber network to a top bearing surface of the implant; infiltrating a hydrogel component into interstitial regions of the cross-linked cellulose nanofiber network to form the cellulose-reinforced hydrogel; as well as The cellulose-reinforced hydrogel is annealed such that the crystal content of the hydrogel component has a crystallinity of 20% or greater.
11. The method of claim 10, wherein the hydrogel component comprises polyvinyl alcohol (PVA).
12. The method of claim 10, wherein annealing the cellulose reinforced hydrogel comprises heating the cellulose reinforced hydrogel.
13. The method of claim 10, wherein annealing the cellulose reinforced hydrogel comprises heating the cellulose reinforced hydrogel to reduce the water content of the cellulose reinforced hydrogel.
14. The method of claim 12, wherein the cellulose reinforced hydrogel is heated to a temperature ranging from 90°C to 140°C.
15. The method of claim 10, wherein annealing the cellulose reinforced hydrogel comprises rehydrating the cellulose reinforced hydrogel.
16. The method of claim 15, wherein rehydrating the cellulose reinforced hydrogel comprises increasing the water content of the cellulose reinforced hydrogel to at least 20 wt.%.
17. The method of claim 10, further comprising removing excess of the hydrogel component from the surface of the cross-linked cellulose nanofiber network.
18. The method of claim 17, wherein excess of the hydrogel components are removed by hand or by molding the cellulose reinforced hydrogel.
19. The method of claim 10, wherein the cross-linked cellulose nanofiber network comprises bacterial cellulose (BC).
20. The method of claim 10, wherein attaching the cross-linked cellulose nanofiber network to the top support surface comprises clamping the cross-linked cellulose nanofibers around a perimeter of the top support surface.
21. An implant for knee resurfacing, the implant comprising: A top support surface comprising a cellulose reinforced hydrogel comprising: Cellulose nanofiber network; and A hydrogel component impregnated in the cellulose nanofiber network, wherein the hydrogel component has a crystallinity of 20% or greater.
22. The method of claim 21, wherein the hydrogel component comprises polyvinyl alcohol (PVA).
23. The implant of claim 21, wherein the cellulose-reinforced hydrogel comprises at least 20% water by weight.
24. The implant of claim 21 , wherein the cellulose reinforced hydrogel has a tensile strength exceeding 40 MPa.
25. The implant of claim 21 wherein the cellulose reinforced hydrogel is attached to the metal base of the top bearing surface with a shear strength exceeding 0.2 MPa.
26. The implant of claim 21 wherein the top bearing surface has a coefficient of friction that is statistically no greater than the coefficient of friction (COF) of cartilage.
27. A cellulose-reinforced hydrogel comprising: a cellulose nanofiber network; and an interstitial hydrogel portion within the interstitial regions of the cellulose nanofiber network, the interstitial hydrogel portion comprising polyvinyl alcohol (PVA), The hydrogel component has a crystallinity of 20% or more.
28. The cellulose-reinforced hydrogel of claim 37, wherein the cellulose nanofiber network comprises at least 20% water by weight.
29. The cellulose-reinforced hydrogel according to claim 27 or 28, wherein the cellulose-reinforced hydrogel has a tensile strength of 40 MPa or greater.
30. The cellulose-reinforced hydrogel according to any one of claims 27-29, wherein the cellulose-reinforced hydrogel has a compressive strength of 59 MPa or greater.